Optical film and flexible display device

An optical film with enhanced mechanical strength and low yellowness is achieved by formulating polyimide resin with specific structural configurations, addressing the limitations of existing films in flexible display devices.

JP7623817B2Active Publication Date: 2025-01-29SUMITOMO CHEM CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020171459
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-31
Filing Date
2020-10-09
Publication Date
2025-01-29
Estimated Expiration
2040-10-09

AI Technical Summary

Technical Problem

Existing optical films used in flexible display devices require improvements in optical characteristics and mechanical strength, particularly in terms of low yellowness and high mechanical strength, to meet the demands of flexible display applications.

Method used

The development of an optical film containing polyimide resin with specific properties, including a tensile strength of 81 MPa or more, an elasticity rate of 4.8 GPA or more, a full light transmittance of 85% or more, and a yellowness index (YI) of less than 3.0, achieved through precise formulation of polyimide resin structures represented by certain chemical configurations.

Benefits of technology

The optical film exhibits excellent mechanical strength, low yellowness, and high transmittance, enhancing visibility and durability in flexible display devices, while reducing power consumption and susceptibility to damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623817000001
    Figure 0007623817000001
  • Figure 0007623817000002
    Figure 0007623817000002
  • Figure 0007623817000003
    Figure 0007623817000003
Patent Text Reader

Abstract

To provide an optical film having low yellowness and excellent folding endurance.SOLUTION: An optical film includes a polyimide-based resin, and has a proof stress in a tensile test of 81 MPa or greater and yellowness of less than 3.0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical film containing a polyimide resin, and a flexible display device including the optical film. [Background technology]

[0002] Display devices such as liquid crystal display devices and organic electroluminescence display devices are widely used for various applications such as mobile phones and smart watches. Glass has been used as the front panel of such display devices, but glass is very rigid and easily broken, making it difficult to use it as the front panel material of flexible display devices. For this reason, optical films using polymers such as polyimide resins and polyamideimide resins have been considered as an alternative material to glass (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2014 / 046180 [Patent Document 2] International Publication No. 2016 / 152459 Summary of the Invention [Problem to be solved by the invention]

[0004] When an optical film containing a polyimide resin is used in, for example, a flexible display device, the optical film is required to have high folding resistance so that the optical properties and mechanical strength of the optical film do not change due to repeated folding. Although various optical films containing polyimide resins have been known, further improvement in the folding resistance of optical films is required.

[0005] In flexible display devices, optical films containing polyimide resins, particularly those used as front panels, are required to have not only high folding resistance but also low yellowness.

[0006] Therefore, an object of the present invention is to provide an optical film having low yellowness and excellent folding resistance. [Means for solving the problem]

[0007] As a result of extensive research aimed at solving the above problems, the present inventors have found that folding endurance can be improved when the yield strength of an optical film is within a predetermined range, and have completed the present invention.

[0008] That is, the present invention includes the following preferred embodiments. [1] An optical film containing a polyimide resin, the film having a yield strength of 81 MPa or more in a tensile test and a yellowness index of less than 3.0. [2] The optical film according to [1] above, having an elastic modulus of 4.8 GPa or more. [3] The optical film according to [1] or [2] above, having a total light transmittance of 85% or more. [4] The optical film according to any one of the above [1] to [3], wherein the polyimide resin has a weight average molecular weight of 100,000 or more. [5] Polyimide resins are represented by the formula (1): [ka] [In formula (1), Y represents a tetravalent organic group, X represents a divalent organic group; * represents a bond. The compound represented by the formula (2): [ka] [In formula (2), R 1 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; R 2 ~R 5 each independently represents a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom; m each independently represents an integer of 0 to 3; n represents an integer of 1 to 4; * represents a bond, except for R 2 ~R 5 In at least one benzene ring having R 2 ~R 5 at least one of the groups is a monovalent hydrocarbon group which may have a halogen atom. The optical film according to any one of the above [1] to [4], which contains a structure represented by the following formula: [6] The optical film according to any one of the above [1] to [5], wherein the polyimide resin is a polyamideimide resin. [7] Polyimide resins are represented by the formula (3): [ka] [In formula (3), Z and X each independently represent a divalent organic group, * represents a bond. The optical film according to any one of the above [1] to [6], which contains a structural unit represented by the following formula: [8] The polyimide resin is represented by the formula (4): [ka] [In formula (4), each W is independently a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO2-, -PO2-, -N(R W1 )- or -Si(R W2 )2-, R W1 and R W2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 8 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; p's each independently represent an integer of 0 to 4; q represents an integer of 0 to 4; * represents a bond. The optical film according to [7] above, comprising a structure represented by the following formula: [9] The optical film according to any one of [1] to [8] above, which is a film for a front panel of a flexible display device.

[10] A flexible display device comprising the optical film according to any one of [1] to [9] above.

[11] The flexible display device according to

[10] , further comprising a touch sensor.

[12] The flexible display device according to

[10] or

[11] , further comprising a polarizing plate. Effect of the Invention

[0009] According to the present invention, it is possible to provide an optical film having low yellowness and excellent folding endurance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.

[0011] [Optical Film] The optical film of the present invention is an optical film containing a polyimide resin, and has a proof stress of 81 MPa or more in a tensile test and a yellowness index of less than 3.

[0012] The optical film of the present invention has a yield strength of 81 MPa or more in a tensile test. If the yield strength is less than 81 MPa, the folding resistance of the optical film cannot be sufficiently improved. The yield strength is preferably 83 MPa or more, more preferably 85 MPa or more, even more preferably 88 MPa or more, even more preferably 90 MPa or more, particularly preferably 93 MPa or more, and particularly preferably 95 MPa or more, and from the viewpoint of the stress required for folding, it is preferably 300 MPa or less, more preferably 250 MPa or less, and even more preferably 200 MPa or less.

[0013] In this specification, the yield strength in the tensile test refers to the yield strength by offset method measured according to ASTM D638-14, and specifically, in the stress-strain curve, a parallel line is drawn from a point on the strain axis corresponding to a permanent strain of 0.2% to the straight line portion at the beginning of the test, and the yield strength can be determined from the stress indicated by the point where the line intersects with the above curve. The yield strength can be measured, for example, using a tensile tester in accordance with ASTM D638-14 Section A2.6. For example, the method described in the Examples may be used as the measurement method.

[0014] Various physical values ​​such as modulus of elasticity have been studied as physical values ​​that may affect the resistance to bending of optical films, but it has been found that sufficient folding resistance may not be achieved simply by improving modulus of elasticity. Therefore, the present inventors have studied various physical values ​​in order to further improve folding resistance, and have found that folding resistance can be sufficiently improved when the strength in a tensile test is 81 MPa or more. The method of adjusting the strength to the above range is not particularly limited, but includes a method of using a polyimide resin as described below.

[0015] The yellowness index (hereinafter, sometimes referred to as YI value) of the optical film of the present invention is less than 3.0. When the YI value is 3.0 or more, the YI value of the optical film is too high, and therefore the visibility when viewing, for example, an image through the optical film is reduced. The YI value of the optical film of the present invention is preferably 2.8 or less, more preferably 2.6 or less, and even more preferably 2.5 or less, and is preferably -5 or more, and more preferably -2 or more, from the viewpoint of easily improving the visibility of an image through the optical film. When the YI value of the optical film is less than the above upper limit, the transparency is good, and when used as a front panel of a display device, it can contribute to high visibility. The YI value can be calculated based on the formula YI=100×(1.2769X-1.0592Z) / Y by measuring the transmittance for light of 300 to 800 nm using an ultraviolet-visible-near infrared spectrophotometer to determine the tristimulus values ​​(X, Y, Z). The method for adjusting the YI value of the optical film to be within the above range is not particularly limited, but examples thereof include a method of using a polyimide resin as described below, a method of adding a blue dye, a method of thinning the film, a method of introducing a side chain into an aromatic ring of a monomer main chain, and the like.

[0016] The elastic modulus of the optical film of the present invention is preferably 4.8 GPa or more, more preferably 5.2 GPa or more, and even more preferably 6.0 GPa or more, and usually 100 GPa or less, from the viewpoint of easily improving the folding resistance of the optical film and easily preventing wrinkles, scratches, etc. The elastic modulus can be measured using a tensile tester (chuck distance 50 mm, tensile speed 10 mm / min), for example, by the method described in the Examples. As a method for increasing the elastic modulus, a method of adding a rigid inorganic filler and a method of introducing a crosslinked structure are known. However, when such a method is used, while the elastic modulus is improved, improvement in strength is often not observed. However, in the optical film of the present invention, it is possible to increase both of them, and further improvement in folding resistance is achieved.

[0017] The optical film of the present invention has excellent folding resistance. The number of folding times of the optical film of the present invention in the MIT folding fatigue test according to ASTM standard D2176-16 is preferably 80,000 times or more, more preferably 100,000 times or more, and even more preferably 250,000 times or more. When the number of folding times is equal to or more than the above lower limit, the occurrence of cracks, breaks, creases, etc. can be effectively suppressed even if the film is repeatedly folded. The MIT folding fatigue test can be measured using an MIT folding fatigue tester, for example, by the method described in the Examples.

[0018] The total light transmittance of the optical film of the present invention is preferably 85% or more, more preferably 88% or more, even more preferably 89% or more, and particularly preferably 90% or more. If the total light transmittance is equal to or more than the above lower limit, the optical film is likely to improve visibility when incorporated into a display device as a front panel. Since the optical film of the present invention usually exhibits high total light transmittance, it is possible to suppress the luminescence intensity of a display element or the like required to obtain a certain brightness, for example, compared with the case where a film with low transmittance is used. This makes it possible to reduce power consumption. For example, when the optical film of the present invention is incorporated into a display device, there is a tendency to obtain a bright display even if the amount of light of the backlight is reduced, which contributes to energy saving. The upper limit of the total light transmittance is usually 100% or less. The total light transmittance can be measured, for example, using a haze computer in accordance with JIS K 7361-1:1997. The total light transmittance may be the total light transmittance in the range of the thickness of the optical film described later. In this specification, an optical film having excellent optical properties means that the total light transmittance is high, and / or the haze is low, and / or the YI value is low, and may be used to mean the same thing as increased or improved transparency.

[0019] The haze of the optical film of the present invention is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, particularly preferably 1% or less, particularly preferably 0.8% or less, particularly preferably 0.5% or less, and is usually 0.01% or more. When the haze of the optical film is within the above range, the optical film is easily improved in visibility when incorporated into a display device, particularly as a front panel. The haze can be measured using a haze computer in accordance with JIS K 7136:2000, for example, by the method described in the Examples.

[0020] The thickness of the optical film of the present invention is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 25 μm or more, particularly preferably 30 μm or more, and is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 80 μm or less, particularly preferably 60 μm or less, and may be a combination of these upper and lower limits. When the thickness of the optical film is within the above range, it is easy to increase the strength and elastic modulus of the optical film. The thickness of the optical film can be measured using a micrometer, for example, by the method described in the Examples.

[0021] The total light transmittance and haze change depending on the thickness of the optical film, and the greater the thickness, the lower the total light transmittance and the higher the haze. That is, it is difficult to produce an optical film with high total light transmittance and low haze in a thick film. In a preferred embodiment of the present invention, the optical film of the present invention has a high level of transparency, so that even if the thickness is relatively large, it can exhibit high total light transmittance and low haze. Therefore, the thickness of the optical film of the present invention is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, even more preferably 25 μm or more, particularly preferably 30 μm or more, particularly preferably 35 μm or more, particularly more preferably 40 μm or more, and preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less. The thickness of the optical film can be measured with a film thickness meter or the like, for example, by the method described in the Examples.

[0022] [Polyimide resin] The optical film of the present invention contains a polyimide resin. The optical film of the present invention may contain one type of polyimide resin, or may contain two or more types of polyimide resin. The content of the polyimide resin in the optical film of the present invention is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, and is preferably 99.5 parts by mass or less, more preferably 95 parts by mass or less, relative to 100 parts by mass of the optical film. When the content of the polyimide resin is within the above range, it is easy to improve the strength, optical properties, impact resistance, and elastic modulus of the optical film.

[0023] The polyimide resin contained in the optical film of the present invention may be at least one resin selected from the group consisting of polyimide resin, polyamideimide resin, and polyamic acid resin. The polyimide resin may be one type of polyimide resin, or two or more types of polyimide resin. The polyimide resin is preferably a polyamideimide resin from the viewpoint of film formability and ease of increasing strength. The polyimide resin is preferably an aromatic polyimide resin. The polyimide resin being aromatic means that preferably 60 mol % or more, more preferably 80 mol % or more, and even more preferably 85 mol % or more of the structural units constituting the polyimide resin are structural units containing an aromatic structure.

[0024] In a preferred embodiment of the present invention, the polyimide resin has the formula (1): [ka] [In formula (1), Y represents a tetravalent organic group, X represents a divalent organic group, and * represents a bond.] or a polyimide resin having a constitutional unit represented by formula (1) and a constitutional unit represented by formula (3): [ka] [In formula (3), Z and X each independently represent a divalent organic group, * represents a bond. It is preferable that the polyamide-imide resin has a structural unit represented by the following formula (1) and formula (3). The explanation of formula (1) relates to both polyimide resins and polyamide-imide resins, and the explanation of formula (3) relates to polyamide-imide resins.

[0025] The structural unit represented by formula (1) is a structural unit formed by the reaction of a tetracarboxylic acid compound with a diamine compound, and the structural unit represented by formula (3) is a structural unit formed by the reaction of a dicarboxylic acid compound with a diamine compound. In a preferred embodiment of the present invention in which the polyimide resin is an aromatic polyimide resin, at least one of the tetracarboxylic acid compound, the diamine compound, and the dicarboxylic acid compound constituting the structural unit represented by formula (1) and the structural unit represented by formula (3) is preferably an aromatic compound (aromatic tetracarboxylic acid compound, aromatic diamine compound, and / or aromatic dicarboxylic acid compound).

[0026] Y in formula (1) represents a tetravalent organic group, preferably a tetravalent organic group having 4 to 80 carbon atoms, more preferably a tetravalent organic group having 4 to 60 carbon atoms and having a cyclic structure. Examples of the cyclic structure include an alicyclic ring, an aromatic ring, and a heterocyclic structure. The organic group is an organic group in which a hydrogen atom in the organic group may be substituted with a substituent, and the substituent is preferably a halogen atom, a monovalent hydrocarbon group (e.g., an alkyl group, an aryl group, etc.) which may have a halogen atom, an alkoxy group, or an aryloxy group. The number of carbon atoms in the monovalent hydrocarbon group, alkoxy group, or aryloxy group which may have a halogen atom as the substituent is preferably 1 to 8. The constitutional unit represented by formula (1) is a repeating unit, and the polyimide resin contained in the optical film of the present invention has a plurality of constitutional units represented by formula (1). In the plurality of constitutional units represented by formula (1), Y may be the same as or different from each other. In other words, the polyimide resin contained in the optical film of the present invention may have one type of structure as Y in formula (1), or may have two or more types of structures.

[0027] In a preferred embodiment of the present invention, from the viewpoint of easily increasing the durability of the obtained optical film, the polyimide resin has a constitutional unit represented by formula (1), and Y in formula (1) is a constitutional unit represented by formula (2): [ka] [In formula (2), R 1 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; R 2 ~R 5 each independently represents a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom; each m independently represents an integer of 0 to 3; n represents an integer of 1 to 4; * represents a bond; provided that R 2 ~R 5 In at least one benzene ring having R 2 ~R 5 at least one of which represents a monovalent hydrocarbon group which may have a halogen atom. or the polyimide resin has a constitutional unit represented by formula (1) and a constitutional unit represented by formula (3), and Z in formula (3) is a structure represented by formula (4″): [ka] [In formula (4"), each W is independently a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R C1 )- or -Si(R C2 )2-, R C1 and R C2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 8’ each independently represents an alkyl group or an alkoxy group which may have a halogen atom; each p' independently represents an integer of 1 to 4; q represents an integer of 0 to 4; and * represents a bond. The compound contains at least a structure (divalent organic group) represented by the following formula:

[0028] The present inventors have found that when a polyimide-based resin contains a structure represented by formula (2) as Y in formula (1), and when a polyimide-based resin has a structural unit represented by formula (1) and a structural unit represented by formula (3) and contains a structure represented by formula (4") as Z in formula (3), the YI of an optical film obtained using the polyimide-based resin is easily reduced and the yield strength is easily increased. In the above cases, the polyimide-based resin contains a structure represented by formula (2) and / or a structure represented by formula (4"). The reason why the inclusion of these structures makes it easier to increase the yield strength is not clear, but both the structure represented by formula (2) and the structure represented by formula (4") have an aromatic main chain and a substituent. Such a structure is a structure that inhibits intermolecular packing because the polyimide resin skeleton is rigid and the side chain has a substituent. It is believed that the inclusion of such a structure in a polyimide resin makes the polyamide resin have a high elastic modulus and high toughness, and the stress until yielding becomes higher. Furthermore, a polyimide resin that has high yield strength by including such a structure makes it easier to increase the transparency of the obtained optical film and also makes it easier to reduce the YI value. As a result, it is possible to achieve both high yield strength and excellent optical properties.

[0029] R in Equation (2) 1are each independently a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom. The alkyl group, alkoxy group, aryl group, or aryloxy group which may have a halogen atom represents an alkyl group which may have a halogen atom, an alkoxy group which may have a halogen atom, an aryl group which may have a halogen atom, or an aryloxy group which may have a halogen atom. This also applies to other similar descriptions. Examples of halogen atoms include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. Examples of alkyl groups include methyl groups, ethyl groups, n-propyl groups, isopropyl groups, n-butyl groups, sec-butyl groups, tert-butyl groups, n-pentyl groups, 2-methyl-butyl groups, 3-methylbutyl groups, 2-ethyl-propyl groups, and n-hexyl groups. Examples of alkoxy groups include methoxy groups, ethoxy groups, propyloxy groups, isopropyloxy groups, butoxy groups, isobutoxy groups, tert-butoxy groups, pentyloxy groups, hexyloxy groups, and cyclohexyloxy groups. Examples of the aryl group include a phenyl group, a tolyl group, a xylyl group, a naphthyl group, and a biphenyl group. Examples of the aryloxy group include a phenoxy group, a naphthyloxy group, and a biphenyloxy group. R 1 each independently represents preferably a halogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an aryloxy group having 6 to 12 carbon atoms.

[0030] In formula (2), m is, independently of one another, an integer of 0 to 3. From the viewpoint of easily increasing the proof stress, elastic modulus, and transparency of an optical film containing a polyimide resin, m is preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.

[0031] In formula (2), R 2 , R 3 , R 4 and R 5each independently represents a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom. Examples of the monovalent hydrocarbon group include an aromatic hydrocarbon group, an alicyclic hydrocarbon group, and an aliphatic hydrocarbon group. Examples of the aromatic hydrocarbon group include aryl groups such as a phenyl group, a tolyl group, a xylyl group, a naphthyl group, and a biphenyl group. Examples of the alicyclic hydrocarbon group include cycloalkyl groups such as a cyclopentyl group and a cyclohexyl group. Examples of the aliphatic hydrocarbon group include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, a 2-methyl-butyl group, a 3-methylbutyl group, a 2-ethyl-propyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, a tert-octyl group, an n-nonyl group, and an n-decyl group. Examples of the halogen atom include those described above. R 2 ~R 5 R each independently represents preferably a hydrogen atom, or an aryl group having 6 to 12 carbon atoms, a cycloalkyl group having 4 to 8 carbon atoms, or an alkyl group having 1 to 6 carbon atoms, which may have a halogen atom. 2 ~R 5 From the viewpoint of easily increasing the solubility of the resin in a solvent and easily improving the proof stress, elastic modulus and transparency of the optical film, each independently preferably represents a hydrogen atom or an alkyl group which may have a halogen atom, more preferably represents a hydrogen atom or an alkyl group having 1 to 6 carbons which may have a halogen atom, and even more preferably represents a hydrogen atom or an alkyl group having 1 to 3 carbons which may have a halogen atom.

[0032] In formula (2), R 2 ~R 5 In at least one benzene ring having R 2 ~R 5 From the viewpoint of easily improving both the durability and optical properties of the optical film, it is preferable that at least one of R represents a monovalent hydrocarbon group which may have a halogen atom. 2 ~R 5 In at least one benzene ring having R2 ~R 5 Preferably, 2 to 4, more preferably 3 or 4, and even more preferably 3 of these are monovalent hydrocarbon groups which may have a halogen atom.

[0033] From the viewpoint of easily increasing the solubility of the resin in a solvent and more easily improving the strength, breaking strain, elastic modulus, and transparency of the optical film, when n is 2 or more, R 2 ~R 5 In at least two benzene rings having R 2 ~R 5 It is more preferable that at least one of R represents a monovalent hydrocarbon group which may have a halogen atom, 2 ~R 5 In all benzene rings having R 2 ~R 5 It is more preferable that at least one of them represents a monovalent hydrocarbon group which may have a halogen atom.

[0034] In formula (2), n represents an integer of 1 to 4, and from the viewpoint of easily improving the elastic modulus and transparency of the optical film and easily improving the durability of the optical film, n is preferably an integer of 1 to 3, more preferably 2 or 3, and further preferably 2. The constitutional unit represented by formula (1) may contain one or more types of structures represented by formula (2) as Y.

[0035] In a preferred embodiment of the present invention, formula (2) is represented by formula (2'): [ka] [In formula (2'), * represents a bond] That is, the polyimide resin contains a structure represented by formula (2') as Y in formula (1). When the polyimide resin contains a structure represented by formula (2') as Y in formula (1), it is easy to improve the yield strength, elastic modulus, and transparency of the optical film.

[0036] In a preferred embodiment of the present invention in which the polyimide resin contains a structure represented by formula (2) as Y in formula (1), the proportion of the structural units represented by formula (1) in which Y in formula (1) is a structure represented by formula (2) (preferably formula (2')) is preferably 30 mol% or more, more preferably 35 mol% or more, and even more preferably 40 mol% or more, relative to the total molar amount (100 mol%) of the structural units represented by formula (1), and is usually 100 mol% or less, preferably 90 mol% or less, more preferably 80 mol% or less, and even more preferably 70 mol% or less. When the proportion of the structural units in which Y is represented by formula (2) is the above lower limit or more, the proof strength and elastic modulus of the optical film are easily increased. Also, when it is the above upper limit or less, the breaking strain and transparency of the optical film are easily increased. The proportion of the structural units in which Y is represented by formula (2) is, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0037] The polyimide resin of the present invention may have a structural unit in which Y in formula (1) represents another tetravalent organic group in addition to or instead of the structural unit represented by formula (2) in formula (1). For example, the tetravalent organic group in Y in formula (1) may be any of the structural units represented by formulas (20), (21), (22), (23), (24), (25), (26), (27), (28) and (29): [ka] Examples of the structure include those represented by the following formula:

[0038] In formulas (20) to (29), * represents a bond, W 1 is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom (e.g., -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-), -Ar-, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R W1 )- or -Si(R W2R represents -O-Ar-O-, -Ar-O-Ar-, -Ar-CH2-Ar-, -Ar-C(CH3)2-Ar-, or -Ar-SO2-Ar-. Ar represents an arylene group having 6 to 20 carbon atoms which may have a fluorine atom, and a specific example thereof is a phenylene group. W1 and R W2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom. The hydrogen atom on the ring in formulae (20) to (29) may be substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. The alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms are each represented by R in formula (2). 1 Examples of such a substance include those exemplified above.

[0039] Among the groups represented by formulae (20) to (29), from the viewpoint of easily improving the strength, breaking strain, elastic modulus and transparency of the optical film, the groups represented by formula (26), formula (28) or formula (29) are preferred, and the group represented by formula (26) is more preferred. 1 From the viewpoint of easily improving the strength, breaking strain, elastic modulus and transparency of the optical film, preferably represents a single bond, -O-, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2- or -C(CF3)2-, more preferably a single bond, -O-, -CH2-, -CH(CH3)-, -C(CH3)2- or -C(CF3)2-, even more preferably a single bond, -C(CH3)2- or -C(CF3)2-, still more preferably a single bond or -C(CF3)2-, particularly preferably -C(CF3)2-. In the above preferred embodiment in which the polyimide resin contains a structure represented by formula (2) as Y in formula (1), the polyimide resin preferably further has a structural unit represented by formula (26) in which Y in formula (1) is in addition to the structural unit represented by formula (2) in which Y in formula (1) is in order to easily improve the strength of the optical film.

[0040] In a preferred embodiment of the present invention, formula (26) is preferably represented by formula (5): [ka] [In formula (5), B is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -COO-, -PO-, -PO2-, -N(R B1 )- or -Si(R B2 )2-, R B1 and R B2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 7 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; each t independently represents an integer of 0 to 3; and * represents a bond. When the polyimide resin has a structural unit in which Y in formula (1) is represented by formula (5), in addition to the structural unit in which Y in formula (1) is represented by formula (2), the solubility of the resin in a solvent and the strength and transparency of the optical film are easily improved.

[0041] R in Equation (5) 7 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom. The halogen atom, the alkyl group, the alkoxy group, the aryl group, and the aryloxy group which may have a halogen atom are each represented by R 1 From the viewpoint of improving the strength, breaking strain, elastic modulus and transparency of the optical film, R 7 each independently represents preferably an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, more preferably an alkyl group having 1 to 3 carbon atoms which may have a halogen atom.

[0042] In formula (5), t's each independently represent an integer of 0 to 3, and from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, are preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.

[0043] In formula (5), B is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -COO-, -PO-, -PO2-, -N(R B1 )- or -Si(R B2 )2-, R B1 and R B2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom.

[0044] The divalent hydrocarbon group which may have a halogen atom is R 2 ~R 5 Among the monovalent hydrocarbon groups which may have a halogen atom in the above formula, a divalent group in which one hydrogen atom has been further removed can be mentioned. The divalent hydrocarbon group which may have a halogen atom can form a ring by replacing two of the hydrogen atoms contained in the group, that is, the two hydrogen atoms can be replaced with bonds and the two bonds can be linked to form a ring. Examples of such rings include a cycloalkane ring having 3 to 12 carbon atoms. In addition, -N(R B1 )- and -Si(R B2 )2-R B1 and R B2 The alkyl group optionally substituted with a halogen atom in formula (3) is 1 Examples of the alkyl group which may have a halogen atom include those exemplified above.

[0045] In terms of easily improving the strength, breaking strain, elastic modulus, and transparency of the optical film, B in formula (5) preferably represents a single bond or a divalent hydrocarbon group which may have a halogen atom, more preferably a single bond, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, or -C(CF3)2-, even more preferably a single bond, -C(CH3)2-, or -C(CF3)2-, still more preferably a single bond or -C(CF3)2-, and particularly preferably -C(CF3)2-.

[0046] In a preferred embodiment of the present invention, formula (5) is represented by formula (5'): [ka] [In formula (5'), * represents a bond] That is, it is preferable that the polyimide resin has a constitutional unit in which Y is represented by formula (5') as at least a part of the constitutional unit represented by formula (1). In this case, it is easy to improve the strength, transparency, elastic modulus and bending resistance of the optical film.

[0047] When the polyimide resin contains a structural unit in which Y in formula (1) is represented by formula (5), the proportion of the structural unit in which Y in formula (1) is a structure represented by formula (5), preferably formula (5'), among the structural units represented by formula (1), is preferably 30 mol% or more, more preferably 35 mol% or more, even more preferably 40 mol% or more, and preferably 90 mol% or less, more preferably 80 mol% or less, and even more preferably 70 mol% or less, relative to the total molar amount (100 mol%) of the structural units represented by formula (1). When the proportion of the structural unit in which Y is represented by formula (5) is the above lower limit or more, the solubility of the resin in a solvent and the transparency of the optical film are easily improved. Also, when it is the above upper limit or less, the proof strength and elastic modulus of the optical film are easily increased. The proportion of the structural unit in which Y in formula (1) is represented by formula (5) is, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0048] In one embodiment of the present invention, when the polyimide resin contains a structural unit in which Y in formula (1) is represented by formula (2) and a structural unit in which Y in formula (1) is represented by formula (5), the total ratio of the structural unit in which Y is represented by formula (2) and the structural unit in which Y is represented by formula (5) is preferably 50 mol% or more, more preferably 70 mol% or more, and even more preferably 90 mol% or more, and usually 100 mol% or less, based on the total molar amount of the structural unit represented by formula (1). When the total ratio is within the above range, the yield strength, breaking strain, elastic modulus, and transparency of the optical film are easily improved. The total ratio may be, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0049] X in formula (1) represents a divalent organic group, preferably a divalent organic group having 4 to 40 carbon atoms. From the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, the polyimide resin of the present invention preferably contains at least one of a divalent aromatic group, a divalent alicyclic group, and a divalent aliphatic group as X in formula (1), and more preferably contains a divalent aromatic group. Examples of the divalent aromatic group include R 2 ~R 5 a divalent aromatic hydrocarbon group in which one of the hydrogen atoms in the monovalent aromatic hydrocarbon group exemplified above is replaced by a bond; 1 Examples of the divalent alicyclic group include a group bonded via a linking group such as R 2 ~R 5 a divalent alicyclic hydrocarbon group in which one of the hydrogen atoms in the monovalent alicyclic hydrocarbon group exemplified above is replaced by a bond; 1 Examples of the divalent aliphatic group include groups bonded via a linking group such as R 2 ~R 5 a divalent aliphatic hydrocarbon group in which one of the hydrogen atoms in the monovalent aliphatic hydrocarbon group exemplified above is replaced by a bond; 1 Examples of such groups include groups bonded via a linking group such as the above.

[0050] X in formula (1) preferably represents a divalent organic group having a cyclic structure (such as an alicyclic, aromatic, or heterocyclic structure) of 4 to 40 carbon atoms, more preferably a divalent aromatic group having 4 to 40 carbon atoms and a divalent alicyclic group having 4 to 40 carbon atoms, and even more preferably a divalent aromatic group having 4 to 40 carbon atoms. The organic group may have a hydrogen atom substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group, and in that case, the number of carbon atoms in the hydrocarbon group and the fluorine-substituted hydrocarbon group is preferably 1 to 8. In one embodiment of the present invention, the polyamideimide resin of the present invention may contain multiple types of X, and the multiple types of X may be the same or different from each other. Examples of X include groups represented by formula (10), formula (11), formula (12), formula (13), formula (14), formula (15), formula (16), formula (17) and formula (18); and groups in which hydrogen atoms in the groups represented by formula (10) to formula (18) are substituted with a methyl group, a fluoro group, a chloro group or a trifluoromethyl group. The hydrogen atoms on the rings in formula (10) to formula (18) may be substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms. The alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms and the aryl group having 6 to 12 carbon atoms are each R in formula (2). 1 Examples of such a substance include those exemplified above.

[0051] [ka]

[0052] In formulas (10) to (18), * represents a bond, V 1 , V 2 and V 3 are each independently a single bond, -O-, -S-, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-, -SO2-, -CO-, or -N(Q)-, where Q is a monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom.

[0053] As the monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom, R2 ~R 5 Examples of the monovalent hydrocarbon group which may have a halogen atom in the formula (I) include those exemplified above.

[0054] One example is V 1 and V 3 is a single bond, -O- or -S-, and V 2 is -CH2-, -C(CH3)2-, -C(CF3)2- or -SO2-. 1 and V 2 The bonding positions of each ring and V 2 and V 3 The bonding positions of each of the rings are, independently of each other, preferably the meta or para position, more preferably the para position, relative to each ring.

[0055] In a preferred embodiment of the present invention, the polyimide resin of the present invention has a structure represented by the formula (6): [ka] [In formula (6), A is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R A1 )- or -Si(R A2 )2-, R A1 and R A2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 6 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; each s independently represents an integer of 0 to 4; and * represents a bond. When the polyimide resin has a structural unit represented by formula (6) in which X in formula (1) is a structural unit represented by formula (6), the strength, breaking strain, elastic modulus, and transparency of the optical film are easily improved. In the present invention, the polyimide resin may contain one or more groups represented by formula (6) as X in the structural unit represented by formula (1).

[0056] R in Equation (6)6 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom. The halogen atom, the alkyl group, the alkoxy group, the aryl group, and the aryloxy group which may have a halogen atom are each represented by R 1 Examples of such a substance include those exemplified above.

[0057] Among these, R 6 each independently represents, from the viewpoint of easily improving the strength, breaking strain, elastic modulus, and transparency of the optical film, preferably an alkyl group having 1 to 6 carbon atoms or a halogenated alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms or a fluoroalkyl group having 1 to 6 carbon atoms (preferably a perfluoroalkyl group). 6 each independently represents a methyl group, a chloro group, or a trifluoromethyl group. Each s independently represents an integer of 0 to 4, and from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, is preferably an integer of 1 to 3, more preferably 1 or 2, and further preferably 1. In a preferred embodiment of the present invention, in each benzene ring, s is 1, and R is located at the ortho position relative to -A-. 6 is substituted and R 6 is preferably a methyl group, a fluoro group, a chloro group or a trifluoromethyl group.

[0058] In formula (6), the positions of the bonds are preferably meta or para, and more preferably para, based on -A-, from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film.

[0059] In formula (6), A is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R A1 )- or -Si(R A2 )2-, R A1 and R A2each independently represents a hydrogen atom or an alkyl group which may have a halogen atom.

[0060] The divalent hydrocarbon group which may have a halogen atom is R in the formula (3). 2 ~R 5 Among the monovalent hydrocarbon groups which may have a halogen atom in the above formula, a divalent group in which one hydrogen atom has been further removed can be mentioned. The divalent hydrocarbon group which may have a halogen atom can form a ring by replacing two of the hydrogen atoms contained in the group, that is, the two hydrogen atoms can be replaced with bonds and the two bonds can be linked to form a ring, and examples of such rings include a cycloalkane ring having 3 to 12 carbon atoms. In addition, -N(R A1 )- and -Si(R A2 )2-R A1 and R A2 The alkyl group which may have a halogen atom in the formula (3) is R 1 Examples of the alkyl group which may have a halogen atom include those exemplified above.

[0061] In terms of easily improving the strength, breaking strain, elastic modulus, and transparency of the optical film, A in formula (6) preferably represents a single bond, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, or -C(CF3)2-, more preferably a single bond, -C(CH3)2-, or -C(CF3)2-, even more preferably a single bond or -C(CF3)2-, and particularly preferably a single bond.

[0062] In a preferred embodiment of the present invention, from the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily improving the yield strength of the optical film, R 6 each independently represents a halogenated alkyl group having 1 to 6 carbon atoms, s is 1 or 2, and A represents a single bond, -C(CH3)2- or -C(CF3)2-.

[0063] In a preferred embodiment of the invention, formula (6) is represented by formula (6'): [ka] That is, at least a part of the multiple Xs in formula (1) is preferably represented by formula (6'). In this form, it is easy to improve the yield strength, breaking strain, elastic modulus, and transparency of the optical film.

[0064] Among the structural units represented by formula (1), the proportion of structural units in which X in formula (1) is a structure represented by formula (6) is preferably 50 mol% or more, more preferably 70 mol% or more, and even more preferably 80 mol% or more, and is usually 100 mol% or less, relative to the total molar amount (100 mol%) of the structural units represented by formula (1). When the proportion of structural units in which X is represented by formula (4) is equal to or more than the above lower limit, the transparency of the optical film is more easily increased. On the other hand, when it is equal to or less than the above upper limit, the strength of the optical film is more easily increased. The proportion of structural units in which X in formula (1) is represented by formula (6) is, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0065] The polyimide resin contained in the optical film of the present invention has, in addition to the structural unit represented by formula (1) as described above, a structural unit represented by formula (3): It may have a constitutional unit represented by the formula (3): TIFF0007623817000016.tif2875. When the polyimide resin has a constitutional unit represented by the formula (3), the resin is also called a polyamideimide resin.

[0066] Z in formula (3) represents a divalent organic group, preferably a divalent organic group having 4 to 40 carbon atoms which may have a hydrocarbon group having 1 to 8 carbon atoms or a fluorine-substituted hydrocarbon group having 1 to 8 carbon atoms, more preferably a divalent organic group having 4 to 40 carbon atoms and having a cyclic structure which may have a hydrocarbon group having 1 to 8 carbon atoms or a fluorine-substituted hydrocarbon group having 1 to 8 carbon atoms. Examples of the cyclic structure include an alicyclic ring, an aromatic ring, and a heterocyclic structure. Examples of the divalent organic group having an alicyclic ring and an aromatic ring include those represented by formulae (20), (21), (22), (23), (24), (25), (26), (27), (28), and (29): [ka] [In formulas (20) to (29), W 1 is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom (e.g., -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-), -Ar-, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R W1 )- or -Si(R W2 )2-, -O-Ar-O-, -Ar-O-Ar-, -Ar-CH2-Ar-, -Ar-C(CH3)2-Ar-, or -Ar-SO2-Ar-, where Ar each independently represents an arylene group having 6 to 20 carbon atoms which may have a fluorine atom, such as a phenylene group; R W1 and R W2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom, and * represents a bond. Examples of the divalent organic group having a heterocyclic structure include a group having a thiophene ring skeleton. From the viewpoint of easily reducing the YI value of the optical film, examples of the divalent organic group having a heterocyclic structure include a group having a thiophene ring skeleton and a group having a thiophene ring skeleton.

[0067] Z in the formula (3) is selected from the group consisting of the formula (20'), the formula (21'), the formula (22'), the formula (23'), the formula (24'), the formula (25'), the formula (26'), the formula (27'), the formula (28') and the formula (29'): [ka] [In formulas (20') to (29'), W 1 and * are as defined in formulas (20) to (29). In addition, the hydrogen atom on the ring in the formulae (20) to (29) and (20') to (29') may be substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. The alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms are each preferably a divalent organic group represented by R in the formula (3). 1 Examples of such a substance include those exemplified above.

[0068] In a preferred embodiment of the present invention, the polyimide resin contained in the optical film of the present invention is represented by the formula (4): [ka] [In formula (4), each W is independently a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO2-, -PO2-, -N(R C1 )- or -Si(R C2 )2-, R C1 and R C2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 8 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; each p independently represents an integer of 0 to 4; q represents an integer of 0 to 4; and * represents a bond. When the polyimide resin has a structural unit represented by formula (3) in which Z is represented by formula (4), the strength, breaking strain, elastic modulus, and transparency of the optical film are easily improved. The structural unit represented by formula (3) may contain one or more groups represented by formula (4) as Z.

[0069] In formula (3), the bonding positions of W are preferably meta or para, and more preferably para, based on the number of bonds, from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, independently of each other.

[0070] In a preferred embodiment of the invention, formula (4) is represented by formula (4'): [ka] [In formula (4'), W, R 8 , p and q are as defined in formula (4). In other words, in at least a part of the constitutional units represented by formula (3) optionally contained in the polyimide resin, Z in formula (3) is preferably represented by formula (4'). In this case, it is easy to improve the yield strength, breaking strain, elastic modulus and transparency of the optical film.

[0071] In formula (4) and formula (4'), R 8 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom. The halogen atom, the alkyl group, the alkoxy group, the aryl group, and the aryloxy group which may have a halogen atom are each represented by R 1 Examples of such a substance include those exemplified above.

[0072] Among these, R 8 each independently represents an integer of 0 to 4, and from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, preferably an alkyl group having 1 to 6 carbon atoms or an alkoxy group having 1 to 6 carbon atoms, which may have a halogen atom, and more preferably an alkyl group having 1 to 3 carbon atoms or an alkoxy group having 1 to 3 carbon atoms. p each independently represents an integer of 0 to 4, and from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, preferably an integer of 0 to 2.

[0073] In the formula (4) and the formula (4'), each W is independently a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO2-, -PO2-, -N(R C1 )- or -Si(R C2From the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, R preferably represents -O- or -S-, and more preferably represents -O-. C1 and R C2 each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom. Examples of the monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom include R in formula (2). 2 ~R 5 Examples of the monovalent hydrocarbon group which may have a halogen atom in the formula (I) include those exemplified above.

[0074] In formulas (4) and (4'), q is an integer ranging from 0 to 4. When q is within this range, the yield strength, breaking strain, elastic modulus, and transparency of the optical film are easily improved. In formulas (4) and (4'), q is preferably an integer ranging from 0 to 3, and more preferably an integer ranging from 0 to 2.

[0075] The constitutional unit represented by formula (4) or formula (4') in which q is 0 is, for example, a constitutional unit derived from terephthalic acid or isophthalic acid, and the constitutional unit is a constitutional unit in which p and q in formula (4) or formula (4') are each 0, or q is 0 and p is 1 or 2 (preferably R 8 is preferably a structural unit in which Z is an alkyl group having 1 to 3 carbon atoms, a fluorinated alkyl group, or an alkoxy group having 1 to 3 carbon atoms. From the viewpoint of easily improving the yield strength, breaking strain, elastic modulus, and transparency of the optical film, it is preferable that the polyamideimide resin contains a structural unit derived from terephthalic acid. The polyamideimide resin may contain one or more structural units represented by formula (4) or formula (4') in Z.

[0076] In one embodiment of the present invention, when Z in formula (3) contains a structure represented by formula (4), the proportion of the structural units represented by formula (3) in which X is represented by formula (4) is preferably 30 mol% or more, more preferably 50 mol% or more, and even more preferably 70 mol% or more, and usually 100 mol% or less, relative to the total molar amount of the structural units represented by formula (3). When the proportion of the structural units represented by formula (4) in formula (3) in which Z is represented by formula (4) is equal to or more than the above lower limit, the breaking strain, elastic modulus, and transparency of the optical film are easily improved, and the strength of the optical film is easily improved. When the proportion is equal to or less than the above upper limit, the viscosity increase of the resin varnish due to hydrogen bonds between amide bonds derived from formula (4) is suppressed, and the processability of the film is easily improved. The proportion of the structural units represented by formula (4) in formula (3) in which Z is represented by formula (4) is, for example, 1 It can be measured by H-NMR, or can be calculated from the ratio of the raw materials. The above description of the preferable ratio also applies to the structure represented by formula (4') and the structure represented by formula (4").

[0077] In one embodiment of the present invention, when the polyimide resin contains a structure represented by formula (4) as Z in formula (3), the ratio of the structural unit represented by formula (3) in which X is represented by formula (4) is preferably 5 mol% or more, more preferably 15 mol% or more, even more preferably 30 mol% or more, particularly preferably 50 mol% or more, and usually 100 mol% or less, based on the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3). When the ratio of the structural unit represented by formula (4) in formula (3) in which Z is represented by formula (4) is the above lower limit or more, the strength, breaking strain, elastic modulus and transparency of the optical film are easily improved. When the ratio is the above upper limit or less, the viscosity increase of the resin varnish due to hydrogen bonding between amide bonds derived from formula (4) is suppressed, and the processability of the film is easily improved. The ratio of the structural unit represented by formula (4) in formula (3) in which Z is represented by formula (4) is, for example, 1 It can be measured by H-NMR, or can be calculated from the ratio of the raw materials. The above description of the preferable ratio also applies to the structure represented by formula (4') and the structure represented by formula (4").

[0078] In the case where Z in the formula (3) has a structural unit represented by any one of the above formulas (20') to (29'), and in the case where Z in the formula (3) has a structural unit represented by formula (4'), the polyamideimide resin further has a structural unit represented by the following formula (d1) in addition to the structural units represented by the formulas (1) and (3): [ka] [In formula (d1), R 24 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms; R 25 is R 24 or -C(=O)-*, where * represents a bond. In order to suppress an increase in the viscosity of the resin varnish due to hydrogen bonding between amide bonds, it is preferable from the viewpoint of film processability.

[0079] R 24 In the formula (2), the alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms are each represented by R 1 Examples of the structural unit (d1) include those exemplified above. Specific examples of the structural unit (d1) include R 24 and R 25 A structural unit in which all of R are hydrogen atoms (a structural unit derived from a dicarboxylic acid compound), 24 are all hydrogen atoms, and R 25 represents -C(=O)-* (a structural unit derived from a tricarboxylic acid compound).

[0080] When the polyamideimide resin contains a structural unit represented by formula (d1), the proportion of the structural unit represented by formula (d1) is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, and even more preferably 1 mol% or more, and is preferably 30 mol% or less, more preferably 20 mol% or less, and even more preferably 10 mol% or less, relative to the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3). When the proportion is within the above range, the viscosity increase of the resin varnish due to hydrogen bonding between amide bonds is suppressed, and the processability of the film is easily improved. In addition, the proportion may be, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0081] In a preferred embodiment of the present invention, the polyimide resin contained in the optical film of the present invention has a constitutional unit represented by formula (1) and a constitutional unit represented by formula (3), and Z in formula (3) is a constitutional unit represented by formula (4″): [ka] [In formula (4"), each W is independently a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R C1 )- or -Si(R C2 )2-, R C1 and R C2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 8’ each independently represents an alkoxy group which may have a halogen atom; each p' independently represents an integer of 1 to 4; q represents an integer of 0 to 4; and * represents a bond. When the polyimide resin contains the structure represented by the above formula (4"), the yield strength of the polyimide resin is easily improved. In addition, the optical properties of the resulting optical film are easily improved.

[0082] The description of W and q in the above formula (4) applies to W and q in the formula (4) as well.8’ each independently represents an alkoxy group which may have a halogen atom, and preferably represents an alkoxy group having 1 to 6 carbon atoms. In formula (4"), each p' independently represents an integer of 1 to 4, and preferably represents an integer of 1 or 2.

[0083] X in formula (3) may be the same as those exemplified above for X in formula (1), and the preferred forms are also the same. X in formula (1) and X in formula (3) may be the same or different. In one embodiment of the present invention, the constitutional unit represented by formula (1) and / or the constitutional unit represented by formula (3) may contain one or more types of structure (or group) represented by formula (5) as X.

[0084] In one embodiment of the present invention, when X in formula (1) and formula (3) contains a structure represented by formula (5), the proportion of the structural unit represented by formula (5) in X is preferably 30 mol% or more, more preferably 50 mol% or more, and even more preferably 70 mol% or more, and usually 100 mol% or less, based on the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3). When the proportion of the structural unit represented by formula (5) in X is within the above range, it is easy to improve the yield strength, breaking strain, elastic modulus, and transparency of the optical film. The proportion of the structural unit represented by formula (5) in X is, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0085] The polyimide resin of the present invention may further contain a constitutional unit represented by formula (30) and / or a constitutional unit represented by formula (31) in addition to the constitutional unit represented by formula (1) and the constitutional unit represented by formula (3) which may be included. [ka]

[0086] In formula (30), Y 1 Y is a tetravalent organic group, preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group.1 Examples of the structural unit represented by formula (30) include groups represented by formula (20), formula (21), formula (22), formula (23), formula (24), formula (25), formula (26), formula (27), formula (28) and formula (29), groups in which hydrogen atoms in the groups represented by formulas (20) to (29) are substituted with methyl groups, fluoro groups, chloro groups or trifluoromethyl groups, and tetravalent chain hydrocarbon groups having 6 or less carbon atoms. In one embodiment of the present invention, the structural unit represented by formula (30) is a structural unit comprising a plurality of types of Y 1 and a plurality of Y 1 may be the same or different from each other.

[0087] In formula (31), Y 2 Y is a trivalent organic group, preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. 2 Examples of the structural unit represented by formula (31) include a group in which any one of the bonds of the groups represented by formula (20), formula (21), formula (22), formula (23), formula (24), formula (25), formula (26), formula (27), formula (28), and formula (29) is replaced with a hydrogen atom, and a trivalent chain hydrocarbon group having 6 or less carbon atoms. In one embodiment of the present invention, the structural unit represented by formula (31) is a group in which any one of the bonds of the groups represented by formula (20), formula (21), formula (22), formula (23), formula (24), formula (25), formula (26), formula (27), formula (28), and formula (29) is replaced with a hydrogen atom. 2 and a plurality of Y 2 may be the same or different from each other.

[0088] In formula (30) and formula (31), X 1 and X 2 are each independently a divalent organic group, and preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. 1 and X 2 Examples of such a group include the groups represented by the above formulae (10), (11), (12), (13), (14), (15), (16), (17) and (18); groups in which hydrogen atoms in the groups represented by the formulae (10) to (18) are substituted with methyl groups, fluoro groups, chloro groups or trifluoromethyl groups; and chain hydrocarbon groups having 6 or less carbon atoms.

[0089] When the polyimide resin contains a structural unit represented by formula (30) and / or a structural unit represented by formula (31), the total proportion of the structural unit represented by formula (30) and the structural unit represented by formula (31) is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, and even more preferably 1 mol% or more, and is preferably 30 mol% or less, more preferably 20 mol% or less, and even more preferably 10 mol% or less, relative to the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3). When the total proportion is within the above range, an optical film with a high elastic modulus is easily obtained. The proportion can be, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0090] When the polyimide resin has a constitutional unit represented by formula (1) and a constitutional unit represented by formula (3), the proportion of the constitutional unit represented by formula (1) is preferably 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, particularly preferably 25 mol% or more, and is preferably 90 mol% or less, more preferably 70 mol% or less, even more preferably 60 mol% or less, particularly preferably 50 mol% or less, based on the total molar amount (100 mol%) of the constitutional unit represented by formula (1) and the constitutional unit represented by formula (3). In the polyamideimide resin, when the proportion of the constitutional unit represented by formula (1) is equal to or more than the above lower limit, thickening due to hydrogen bonding between amide bonds in formula (2) can be suppressed, the viscosity of the polyamideimide varnish can be reduced, and the optical member can be easily manufactured. In the polyamideimide resin, when the proportion of the constitutional unit represented by formula (1) is equal to or less than the above upper limit, the optical film comprising the polyamideimide resin exhibits high surface hardness. The proportion can be, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.

[0091] The weight average molecular weight (hereinafter sometimes referred to as Mw) of the polyimide resin contained in the optical film of the present invention is preferably 100,000 or more, more preferably 150,000 or more, even more preferably 200,000 or more, even more preferably 300,000 or more, particularly more preferably 400,000 or more, particularly more preferably 500,000 or more, and especially more preferably 600,000 or more, and is preferably 1,500,000 or less, more preferably 1,200,000 or less, even more preferably 1,000,000 or less, and especially preferably 800,000 or less. When the Mw of the polyimide resin is the above lower limit or more, the yield strength, breaking strain and elastic modulus of the obtained optical film are easily improved. Also, when the Mw is the above upper limit or less, the gelation of the resin varnish is easily suppressed, and the optical properties of the obtained optical film are easily improved. Here, it was found that when the polyimide resin of the present invention contains a structure represented by formula (2) as Y in formula (1), the viscosity of the solution of the polyimide resin having the structure tends to be high. Since the viscosity of the resin solution also tends to be high when the Mw of the polyimide resin is large, it has been very difficult to increase the molecular weight of the polyimide resin containing such a structure. As a result of various studies, the present inventors have found that Mw can be increased by producing a polyimide resin under the production conditions described below. Mw can be determined, for example, by gel permeation chromatography (hereinafter sometimes referred to as GPC) measurement and converted into standard polystyrene, for example, by the method described in the Examples.

[0092] In a preferred embodiment of the present invention, the polyimide resin in the present invention may contain halogen atoms such as fluorine atoms, which can be introduced, for example, by the above-mentioned fluorine-containing substituents. When the polyimide resin contains halogen atoms, the YI value of the optical film is easily reduced, and the breaking strain and elastic modulus are easily increased. When the elastic modulus of the optical film is high, the occurrence of scratches and wrinkles is easily suppressed. In addition, when the YI value of the optical film is low, the transparency and visibility of the film are easily improved. The halogen atom is preferably a fluorine atom. Examples of fluorine-containing substituents that are preferable for containing fluorine atoms in the polyimide resin include a fluoro group and a trifluoromethyl group.

[0093] When the polyimide resin contains halogen atoms, the content is preferably 1 to 40 mass%, more preferably 5 to 40 mass%, and further preferably 5 to 30 mass%, based on the mass of the polyimide resin. When the content of halogen atoms is equal to or more than the above lower limit, the YI value of the optical film is easily reduced and the breaking strain and elastic modulus are easily increased. When the content of halogen atoms is equal to or less than the above upper limit, synthesis is facilitated.

[0094] The imidization rate of the polyimide resin is preferably 90% or more, more preferably 93% or more, and even more preferably 96% or more. From the viewpoint of easily increasing the strength and optical properties of the optical film, it is preferable that the imidization rate is the above lower limit or more. In addition, the upper limit of the imidization rate is 100% or less. The imidization rate indicates the ratio of the molar amount of imide bonds in the polyimide resin to twice the molar amount of the constituent units derived from the tetracarboxylic acid compound in the polyimide resin. In addition, when the polyimide resin contains a tricarboxylic acid compound, it indicates the ratio of the molar amount of imide bonds in the polyimide resin to the sum of twice the molar amount of the constituent units derived from the tetracarboxylic acid compound in the polyimide resin and the molar amount of the constituent units derived from the tricarboxylic acid compound. In addition, the imidization rate can be determined by IR method, NMR method, etc.

[0095] <Method of manufacturing polyimide resin> The method for producing the polyimide resin of the present invention is not particularly limited. In one embodiment of the present invention, the polyimide resin can be produced by using a tetracarboxylic acid compound and a diamine compound described later as main raw materials, and optionally a dicarboxylic acid compound. More specifically, the polyimide resin can be produced by a method including a step of reacting a diamine compound with a tetracarboxylic acid compound to obtain a polyamic acid, a step of reacting the polyamic acid with a dicarboxylic acid to obtain a polyamideimide resin precursor when the polyimide resin is a polyamideimide resin, and a step of imidizing the polyamic acid or the polyamideimide resin precursor. In addition to the tetracarboxylic acid compound and the dicarboxylic acid compound, a tricarboxylic acid compound may be reacted.

[0096] The structural units represented by formula (1) and formula (30) are usually derived from a diamine compound and a tetracarboxylic acid compound. The structural unit represented by formula (3) is usually derived from a diamine compound and a dicarboxylic acid compound. The structural unit represented by formula (31) is usually derived from a diamine compound and a tricarboxylic acid compound.

[0097] The tetracarboxylic acid compound used in the production of the polyimide resin is at least a compound represented by the formula (X): [ka] [In formula (X), R 1 ~R 5 , m and n are R in formula (3), 1 ~R 5 , m and n] It is preferable that the compound contains a compound represented by the following formula:

[0098] The compound represented by formula (X) may be obtained by a conventional method, for example, by reacting trimellitic anhydride or a derivative thereof with an aromatic diol, or a commercially available product may be used.

[0099] In one embodiment of the present invention, the tetracarboxylic acid compound used in the production of the polyimide resin further contains, in addition to the compound represented by formula (X), a compound represented by formula (Y): [ka] [In formula (Y), B, R 7 and t are B and R in formula (5), respectively. 7 and t] It is preferable that the compound contains a compound represented by the following formula:

[0100] The tetracarboxylic acid compound used in the production of the polyimide resin includes aromatic tetracarboxylic acid compounds such as aromatic tetracarboxylic acid dianhydrides; and aliphatic tetracarboxylic acid compounds such as aliphatic tetracarboxylic acid dianhydrides. The tetracarboxylic acid compounds may be used alone or in combination of two or more. The tetracarboxylic acid compounds may be dianhydrides or tetracarboxylic acid compound analogues such as acid chloride compounds.

[0101] Specific examples of aromatic tetracarboxylic dianhydrides include non-condensed polycyclic aromatic tetracarboxylic dianhydrides, monocyclic aromatic tetracarboxylic dianhydrides, and condensed polycyclic aromatic tetracarboxylic dianhydrides. Examples of non-condensed polycyclic aromatic tetracarboxylic dianhydrides include an ester of trimellitic anhydride and 2,2',3,3',5,5'-hexamethyl-4,4'-biphenol (hereinafter sometimes referred to as TAHMBP), an ester of trimellitic anhydride and 2,2',3,3'-tetramethyl-4,4'-biphenol (hereinafter sometimes referred to as TA23X-BP), an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol (hereinafter sometimes referred to as TA23X-BP), and an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol (hereinafter sometimes referred to as TA23X-BP). Esterification with methyl-4,4'-biphenol, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride (hereinafter sometimes referred to as BPDA), 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonate 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (hereinafter sometimes referred to as 6FDA), 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis (2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride, and 4,4'-(m-phenylenedioxy)diphthalic dianhydride.In addition, an example of a monocyclic aromatic tetracarboxylic dianhydride is 1,2,4,5-benzenetetracarboxylic dianhydride (also referred to as pyromellitic dianhydride (hereinafter, sometimes referred to as PMDA)). An example of a condensed polycyclic aromatic tetracarboxylic dianhydride is 2,3,6,7-naphthalenetetracarboxylic dianhydride.

[0102] Among these, preferred are TAHMBP, TA23X-BP, ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, PMDA, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2', 3,3'-Biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, 6FDA, 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1- Bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride, and 4,4'-(m-phenylenedioxy)diphthalic dianhydride. Anhydrides, more preferably TAHMBP, TA23X-BP, esters of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, 4,4'-oxydiphthalic dianhydride, BPDA, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 6FDA, bis(3,4-dicarboxyphenyl)methane dianhydride, and 4,4'-(p-phenylenedioxy)diphthalic dianhydride, can be used alone or in combination of two or more.

[0103] Examples of the aliphatic tetracarboxylic dianhydride include cyclic or non-cyclic aliphatic tetracarboxylic dianhydrides. The cyclic aliphatic tetracarboxylic dianhydride is a tetracarboxylic dianhydride having an alicyclic hydrocarbon structure, and specific examples thereof include cycloalkane tetracarboxylic dianhydrides such as 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride, and 1,2,3,4-cyclopentane tetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride, and positional isomers thereof. These can be used alone or in combination of two or more. Specific examples of the non-cyclic aliphatic tetracarboxylic dianhydride include 1,2,3,4-butane tetracarboxylic dianhydride and 1,2,3,4-pentane tetracarboxylic dianhydride, and the like, and these can be used alone or in combination of two or more. Furthermore, a cyclic aliphatic tetracarboxylic acid dianhydride and a non-cyclic aliphatic tetracarboxylic acid dianhydride may be used in combination.

[0104] Among the above tetracarboxylic dianhydrides, from the viewpoint of easily improving the strength and transparency of the optical film, TAHMBP, TA23X-BP, an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, PMDA, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 6FDA, and mixtures thereof are preferred, and TAHMBP, TA23X-BP, an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, 6FDA, and mixtures thereof are more preferred.

[0105] When the polyimide resin is a polyamide-imide resin, the dicarboxylic acid compound used in the synthesis thereof may include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and their related acid chloride compounds, acid anhydrides, etc., and may be used in combination of two or more.Specific examples include dicarboxylic acid compounds of terephthalic acid, 2,5-bis(trifluoromethyl)terephthalic acid, isophthalic acid, 2,5-dimethylterephthalic acid, 2,5-dimethoxyterephthalic acid, naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 3,3'-biphenyldicarboxylic acid, 2,2'-bis(trifluoromethyl)-4,4'-biphenyldicarboxylic acid, and chain hydrocarbons having 8 or less carbon atoms, and compounds in which two benzoic acids are linked by a single bond, -CH2-, -C(CH3)2-, -C(CF3)2-, -SO2-, or a phenylene group, and acid chloride compounds thereof. Among these dicarboxylic acid compounds, from the viewpoint of easily improving the durability and transparency of the optical film, 4,4'-oxybisbenzoic acid, terephthalic acid, isophthalic acid, 2-methoxyterephthalic acid, 2,5-dimethylterephthalic acid, 2,5-dimethoxyterephthalic acid, 2,5-bis(trifluoromethyl)terephthalic acid, 2,2'-bis(trifluoromethyl)-4,4'-biphenyldicarboxylic acid, and acid chlorides thereof are preferred, and 4,4'-oxybis(benzoyl chloride), 2,5 2,5-dimethylterephthalic acid chloride (hereinafter sometimes referred to as DMTPC), 2,5-dimethoxyterephthalic acid chloride, 2,5-bis(trifluoromethyl)terephthalic acid chloride, 2-methoxyterephthalic acid chloride (hereinafter sometimes referred to as OMTPC), terephthaloyl chloride (hereinafter sometimes referred to as TPC), and isophthaloyl chloride are more preferred, and TPC, 2,5-dimethoxyterephthalic acid chloride, DMTPC, and OMTPC are even more preferred.

[0106] The polyimide-based resin may be a product obtained by further reacting, in addition to the tetracarboxylic acid compound used in the synthesis of the polyimide-based resin, other tetracarboxylic acids and tricarboxylic acids, as well as anhydrides and derivatives thereof, within the range that does not impair various physical properties of the optical film.

[0107] Other tetracarboxylic acids include water adducts of the anhydrides of the above tetracarboxylic acid compounds.

[0108] Examples of tricarboxylic acid compounds include aromatic tricarboxylic acids, aliphatic tricarboxylic acids, and their related acid chloride compounds, acid anhydrides, etc., and two or more of them may be used in combination.Specific examples include anhydride of 1,2,4-benzenetricarboxylic acid; 2,3,6-naphthalenetricarboxylic-2,3-anhydride; and a compound in which phthalic anhydride and benzoic acid are linked by a single bond, -O-, -CH2-, -C(CH3)2-, -C(CF3)2-, -SO2-, or a phenylene group.

[0109] Examples of diamine compounds used in the synthesis of polyimide resins include aliphatic diamines, aromatic diamines, and mixtures thereof. In this embodiment, the term "aromatic diamine" refers to a diamine in which an amino group is directly bonded to an aromatic ring, and may include an aliphatic group or other substituents in a part of its structure. The aromatic ring may be a single ring or a condensed ring, and examples include a benzene ring, a naphthalene ring, an anthracene ring, and a fluorene ring, but are not limited to these. Among these, a benzene ring is preferable. The term "aliphatic diamine" refers to a diamine in which an amino group is directly bonded to an aliphatic group, and may include an aromatic ring or other substituents in a part of its structure.

[0110] Examples of the aliphatic diamine include acyclic aliphatic diamines such as hexamethylenediamine, and cyclic aliphatic diamines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, norbornanediamine, and 4,4'-diaminodicyclohexylmethane. These can be used alone or in combination of two or more.

[0111] Examples of the aromatic diamine include aromatic diamines having one aromatic ring, such as p-phenylenediamine, m-phenylenediamine, 2,4-toluenediamine, m-xylylenediamine, p-xylylenediamine, 1,5-diaminonaphthalene, and 2,6-diaminonaphthalene; 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, and the like. Examples of aromatic diamines having two or more aromatic rings include aromatic diamines having two or more aromatic rings, such as 2,2-bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl (hereinafter sometimes referred to as TFMB), 4,4'-(hexafluoropropylidene)dianiline (hereinafter sometimes referred to as 6FDAM), 4,4'-bis(4-aminophenoxy)biphenyl, 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-chlorophenyl)fluorene, and 9,9-bis(4-amino-3-fluorophenyl)fluorene. These can be used alone or in combination of two or more.

[0112] The aromatic diamine is preferably 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2 More preferred are 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylsulfone, 1,4-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-dimethylbenzidine, TFMB, 6FDAM, and 4,4'-bis(4-aminophenoxy)biphenyl. These can be used alone or in combination of two or more.

[0113] Among the above diamine compounds, from the viewpoint of easily improving the durability and transparency of the optical film, it is more preferable to use one or more selected from the group consisting of 2,2'-dimethylbenzidine, TFMB, 4,4'-bis(4-aminophenoxy)biphenyl, 6FDAM and 4,4'-diaminodiphenyl ether, and it is even more preferable to use TFMB and / or 6FDAM.

[0114] In the production of a polyimide resin, the amounts of the diamine compound, tetracarboxylic acid compound and dicarboxylic acid compound used can be appropriately selected depending on the desired ratio of each structural unit of the resin.

[0115] In a preferred embodiment of the present invention, the amount of the diamine compound used is preferably 0.94 mol or more, more preferably 0.96 mol or more, even more preferably 0.98 mol or more, particularly preferably 0.99 mol or more, and preferably 1.20 mol or less, more preferably 1.10 mol or less, even more preferably 1.05 mol or less, particularly preferably 1.02 mol or less, based on the total molar amount of the tetracarboxylic acid compound and the dicarboxylic acid compound optionally contained, being 1 mol. When the amount of the diamine compound used relative to the tetracarboxylic acid compound and the dicarboxylic acid compound optionally contained is within the above range, even when the polyimide resin has a structure represented by formula (2), a high molecular weight polyimide resin is easily obtained, and as a result, the proof stress and transparency of the obtained optical film are easily improved.

[0116] The reaction temperature between the diamine compound and the tetracarboxylic acid compound is not particularly limited and may be, for example, 5 to 200° C., and the reaction time is also not particularly limited and may be, for example, about 30 minutes to 72 hours. In a preferred embodiment of the present invention, even when the polyimide resin has a structure represented by formula (2), from the viewpoint of easily increasing the Mw of the polyimide resin, the reaction temperature is preferably 5 to 50° C., more preferably 5 to 40° C., and even more preferably 5 to 25° C., and the reaction time is preferably 3 to 24 hours, and more preferably 5 to 20 hours.

[0117] The reaction between the diamine compound and the tetracarboxylic acid compound is preferably carried out in a solvent. The solvent is not particularly limited as long as it does not affect the reaction, and examples of the solvent include alcohol-based solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester-based solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, γ-valerolactone, propylene glycol methyl ether acetate, and ethyl lactate; acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, methyl isobutyric acid, and the like. Examples of suitable solvents include ketone-based solvents such as ethyl ketone, aliphatic hydrocarbon solvents such as pentane, hexane, and heptane, alicyclic hydrocarbon solvents such as ethylcyclohexane, aromatic hydrocarbon solvents such as toluene and xylene, nitrile-based solvents such as acetonitrile, ether-based solvents such as tetrahydrofuran and dimethoxyethane, chlorine-containing solvents such as chloroform and chlorobenzene, amide-based solvents such as N,N-dimethylacetamide (hereinafter sometimes referred to as DMAc) and N,N-dimethylformamide (hereinafter sometimes referred to as DMF), sulfur-containing solvents such as dimethylsulfone, dimethylsulfoxide, and sulfolane, carbonate-based solvents such as ethylene carbonate and propylene carbonate, and combinations thereof. Among these, amide-based solvents can be preferably used from the viewpoint of solubility.

[0118] In a preferred embodiment of the present invention, the solvent used in the reaction is preferably a solvent that has been thoroughly dehydrated to a water content of 700 ppm or less. By adjusting the water content to the above range, even if the polyimide resin has a structure represented by formula (2), the polyimide resin can be easily polymerized.

[0119] The reaction of the diamine compound with the tetracarboxylic acid compound may be carried out, as necessary, in an inert atmosphere such as a nitrogen atmosphere or an argon atmosphere, or under reduced pressure conditions. From the viewpoint of facilitating the production of a high-molecular-weight polyimide resin, it is preferable to carry out the reaction under stirring in a strictly controlled dehydrated solvent under the same inert atmosphere as above.

[0120] The production conditions for the polyamic acid and the dicarboxylic acid may be appropriately selected from the production conditions for the reaction of the diamine compound and the tetracarboxylic acid compound.

[0121] Examples of the imidization catalyst used in the imidization step include aliphatic amines such as tripropylamine, dibutylpropylamine, and ethyldibutylamine; alicyclic amines (monocyclic) such as N-ethylpiperidine, N-propylpiperidine, N-butylpyrrolidine, N-butylpiperidine, and N-propylhexahydroazepine; azabicyclo[2.2.1]heptane, azabicyclo[3.2.1]octane, azabicyclo[2.2.2]octane, and azabicyclo[2.2.3]octane. [3.2.2] Alicyclic amines (polycyclic) such as nonane; and aromatic amines such as pyridine, 2-methylpyridine (2-picoline), 3-methylpyridine (3-picoline), 4-methylpyridine (4-picoline), 2-ethylpyridine, 3-ethylpyridine, 4-ethylpyridine, 2,4-dimethylpyridine, 2,4,6-trimethylpyridine, 3,4-cyclopentenopyridine, 5,6,7,8-tetrahydroisoquinoline, and isoquinoline. In addition, from the viewpoint of facilitating the imidization reaction, it is preferable to use an acid anhydride together with the imidization catalyst. Examples of the acid anhydride include conventional acid anhydrides used in imidization reactions, and specific examples thereof include aliphatic acid anhydrides such as acetic anhydride, propionic anhydride, and butyric anhydride, and aromatic acid anhydrides such as phthalic acid.

[0122] In a preferred embodiment of the present invention, it is preferable to carry out the imidization step stepwise and raise the temperature to an optimal reaction temperature. By carrying out the imidization stepwise, decomposition of the resin is suppressed, and a high molecular weight polyimide resin is easily obtained. The reaction temperature to be raised in the stepwise imidization step is preferably 40 to 85°C, more preferably 45 to 80°C. When the reaction temperature is within the above range, the imidization reaction tends to proceed sufficiently, and Mw tends to increase sufficiently. The reaction time is preferably 30 minutes to 10 hours, more preferably 30 minutes to 5 hours. When the reaction time is within the above range, it is easy to suppress the decomposition of the resin and the decrease in Mw, and it is also easy to suppress the decrease in the imidization rate and the resulting low molecular weight in the subsequent step. In this way, by controlling the imidization step in addition to the synthesis conditions already described, a high molecular weight resin can be obtained.

[0123] The polyimide resin may be isolated by separation and purification using a conventional method, for example, a separation means such as filtration, concentration, extraction, crystallization, recrystallization, column chromatography, or a combination of these. In a preferred embodiment, the resin can be isolated by adding a large amount of alcohol such as methanol to a reaction solution containing the resin to precipitate the resin, and then concentrating, filtering, drying, or the like.

[0124] <Additives> The optical film of the present invention may contain at least one filler in addition to the polyimide resin. Examples of the filler include organic particles and inorganic particles, and preferably inorganic particles. Examples of the inorganic particles include metal oxide particles such as silica, zirconia, alumina, titania, zinc oxide, germanium oxide, indium oxide, tin oxide, indium tin oxide, antimony oxide, and cerium oxide, and metal fluoride particles such as magnesium fluoride and sodium fluoride. Among these, from the viewpoint of easily improving the strength, elastic modulus, and transparency of the optical film, silica particles, zirconia particles, and alumina particles are preferred, and silica particles are more preferred. These fillers can be used alone or in combination of two or more.

[0125] The average primary particle diameter of the filler, preferably silica particles, is usually 1 nm or more, preferably 5 nm or more, more preferably 10 nm or more, even more preferably 15 nm or more, particularly preferably 20 nm or more, and preferably 100 nm or less, more preferably 90 nm or less, even more preferably 80 nm or less, even more preferably 70 nm or less, especially preferably 60 nm or less, especially more preferably 50 nm or less, especially more preferably 40 nm or less. When the average primary particle diameter of the filler, preferably silica particles, is within the above range, it is easy to improve the strength, elastic modulus, and transparency of the optical film. In addition, it is easy to suppress the aggregation of the filler, preferably silica particles, and improve the transparency of the obtained optical film. The average primary particle diameter of the filler can be measured by the BET method. The average primary particle diameter may be measured by image analysis of a transmission electron microscope or a scanning electron microscope.

[0126] When the optical film of the present invention contains a filler, preferably silica particles, the content of the filler is usually 0.1% by mass or more, preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, even more preferably 20% by mass or more, particularly preferably 30% by mass or more, and preferably 60% by mass or less, based on the mass of the optical film. When the content of the filler is equal to or more than the lower limit, the strength, elastic modulus, and transparency of the optical film are easily improved. When the content of the filler is equal to or less than the upper limit, the optical properties of the optical film are easily improved.

[0127] The optical film of the present invention may further contain an ultraviolet absorber. The ultraviolet absorber may be appropriately selected from those that are commonly used as ultraviolet absorbers in the field of resin materials. The ultraviolet absorber may contain a compound that absorbs light with a wavelength of 400 nm or less. Examples of the ultraviolet absorber include at least one compound selected from the group consisting of benzophenone-based compounds, salicylate-based compounds, benzotriazole-based compounds, and triazine-based compounds. The ultraviolet absorbers may be used alone or in combination of two or more. When the optical film contains an ultraviolet absorber, deterioration of the resin is suppressed, so that visibility can be improved when the optical film is applied to an image display device or the like. In this specification, the term "based compound" refers to a derivative of the compound to which the term "based compound" is attached. For example, the term "benzophenone-based compound" refers to a compound having benzophenone as a parent skeleton and a substituent bonded to benzophenone.

[0128] When the optical film contains an ultraviolet absorbing agent, the content of the ultraviolet absorbing agent is preferably 1 mass% or more, more preferably 2 mass% or more, and even more preferably 3 mass% or more, and is preferably 10 mass% or less, more preferably 8 mass% or less, and even more preferably 6 mass% or less, relative to the mass of the optical film. The suitable content varies depending on the ultraviolet absorbing agent used, but adjusting the content of the ultraviolet absorbing agent so that the light transmittance at 400 nm is about 20 to 60% increases the light resistance of the optical film and also makes it easy to increase the transparency.

[0129] The optical film of the present invention may further contain other additives other than the filler and the UV absorber. Examples of the other additives include antioxidants, release agents, stabilizers, bluing agents, flame retardants, pH adjusters, silica dispersants, lubricants, thickeners, and leveling agents. When other additives are contained, the content thereof may be preferably 0.001 to 20% by mass, more preferably 0.01 to 15% by mass, and even more preferably 0.1 to 10% by mass, based on the mass of the optical film.

[0130] The use of the optical film of the present invention is not particularly limited, and it may be used for various purposes. The optical film of the present invention may be a single layer or a laminate, and the optical film of the present invention may be used as it is, or may be used as a laminate with other films. In addition, when the optical film is a laminate, all layers laminated on one side or both sides of the optical film are called the optical film.

[0131] When the optical film of the present invention is a laminate, it is preferable that the optical film has one or more functional layers on at least one surface thereof. Examples of the functional layer include a hard coat layer, a primer layer, a gas barrier layer, an ultraviolet absorbing layer, an adhesive layer, a hue adjusting layer, and a refractive index adjusting layer. The functional layers can be used alone or in combination of two or more kinds.

[0132] The thickness of the hard coat layer is not particularly limited, and may be, for example, 2 to 100 μm. When the thickness of the hard coat layer is within the above range, the impact resistance can be increased, and the bending resistance is not likely to decrease, and the problem of curling due to curing shrinkage tends to be unlikely to occur. The hard coat layer can be formed by curing a hard coat composition containing a reactive material that can form a crosslinked structure by irradiation with active energy rays or by applying thermal energy, and is preferably formed by irradiation with active energy rays. The active energy rays are defined as energy rays that can decompose a compound that generates active species to generate active species, and examples of such rays include visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays, and electron beams, and preferably ultraviolet rays. The hard coat composition contains at least one polymer of a radical polymerizable compound and a cationic polymerizable compound.

[0133] The radical polymerizable compound is a compound having a radical polymerizable group. The radical polymerizable group of the radical polymerizable compound may be any functional group capable of generating a radical polymerization reaction, and may include a group containing a carbon-carbon unsaturated double bond, and specifically includes a vinyl group and a (meth)acryloyl group. When the radical polymerizable compound has two or more radical polymerizable groups, these radical polymerizable groups may be the same or different. The number of radical polymerizable groups that the radical polymerizable compound has in one molecule is preferably 2 or more from the viewpoint of improving the hardness of the hard coat layer. From the viewpoint of high reactivity, the radical polymerizable compound is preferably a compound having a (meth)acryloyl group, and specifically includes compounds called polyfunctional acrylate monomers having 2 to 6 (meth)acryloyl groups in one molecule, and oligomers having several (meth)acryloyl groups in the molecule and having a molecular weight of several hundred to several thousand, called epoxy (meth)acrylates, urethane (meth)acrylates, and polyester (meth)acrylates, and preferably includes one or more types selected from epoxy (meth)acrylates, urethane (meth)acrylates, and polyester (meth)acrylates.

[0134] The cationic polymerizable compound is a compound having a cationic polymerizable group such as an epoxy group, an oxetanyl group, a vinyl ether group, etc. The number of cationic polymerizable groups that the cationic polymerizable compound has in one molecule is preferably 2 or more, more preferably 3 or more, from the viewpoint of improving the hardness of the hard coat layer. Among the cationic polymerizable compounds, compounds having at least one of epoxy and oxetanyl groups as cationic polymerizable groups are preferred. Cyclic ether groups such as epoxy and oxetanyl groups are preferred because they cause little shrinkage during polymerization. Among cyclic ether groups, compounds having epoxy groups are easily available in a variety of structures, and have the advantage that they do not adversely affect the durability of the obtained hard coat layer, and the compatibility with the radical polymerizable compound is easy to control. Among cyclic ether groups, oxetanyl groups tend to have a higher degree of polymerization than epoxy groups, and have the advantage of accelerating the network formation rate obtained from the cationic polymerizable compound of the obtained hard coat layer, and forming an independent network without leaving unreacted monomers in the film even in the region where the radical polymerizable compound is mixed. Examples of the cationically polymerizable compound having an epoxy group include alicyclic epoxy resins obtained by epoxidizing a polyglycidyl ether of a polyhydric alcohol having an alicyclic ring or a compound containing a cyclohexene ring or a cyclopentene ring with a suitable oxidizing agent such as hydrogen peroxide or a peracid; aliphatic epoxy resins such as polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts, polyglycidyl esters of aliphatic long-chain polybasic acids, and homopolymers and copolymers of glycidyl (meth)acrylate; glycidyl ethers produced by reacting bisphenols such as bisphenol A, bisphenol F, and hydrogenated bisphenol A, or derivatives thereof such as alkylene oxide adducts or caprolactone adducts, with epichlorohydrin, and novolak epoxy resins, and the like, which are derived from bisphenols.

[0135] The hard coat composition may further include a polymerization initiator. The polymerization initiator may be a radical polymerization initiator, a cationic polymerization initiator, a radical and cationic polymerization initiator, etc., and may be appropriately selected and used. These polymerization initiators are decomposed by at least one of active energy ray irradiation and heating, generating radicals or cations to promote radical polymerization and cationic polymerization. The radical polymerization initiator may be any initiator capable of releasing a substance that initiates radical polymerization by at least one of irradiation with active energy rays and heating. For example, examples of thermal radical polymerization initiators include organic peroxides such as hydrogen peroxide and perbenzoic acid, and azo compounds such as azobisbutyronitrile. Active energy ray radical polymerization initiators include Type 1 radical polymerization initiators, which generate radicals by molecular decomposition, and Type 2 radical polymerization initiators, which coexist with tertiary amines to generate radicals through a hydrogen abstraction reaction. These are used alone or in combination. The cationic polymerization initiator may be any one that can release a substance that initiates cationic polymerization by at least one of active energy ray irradiation and heating. As the cationic polymerization initiator, aromatic iodonium salts, aromatic sulfonium salts, cyclopentadienyl iron (II) complexes, etc. can be used. These can initiate cationic polymerization by either active energy ray irradiation or heating, or both, depending on the difference in structure.

[0136] The polymerization initiator can be preferably contained in an amount of 0.1 to 10% by mass relative to 100% by mass of the entire hard coat composition. When the content of the polymerization initiator is within the above range, curing can be sufficiently promoted, the mechanical properties and adhesive strength of the finally obtained coating film can be in a good range, and poor adhesive strength, cracking, and curling due to cure shrinkage tend to be unlikely to occur.

[0137] The hard coat composition may further include at least one selected from the group consisting of a solvent and an additive. The solvent can dissolve or disperse the polymerizable compound and the polymerization initiator, and any solvent known in the art as a solvent for hard coat compositions can be used as long as it does not impair the effects of the present invention. The additives may further include inorganic particles, leveling agents, stabilizers, surfactants, antistatic agents, lubricants, antifouling agents, and the like.

[0138] The ultraviolet absorbing layer is a layer having the function of absorbing ultraviolet rays, and is composed of a main material selected from, for example, an ultraviolet curable transparent resin, an electron beam curable transparent resin, and a thermosetting transparent resin, and an ultraviolet absorber dispersed in the main material.

[0139] The adhesive layer is a layer having an adhesive function, and has a function of adhering the optical film to other members. As a material for forming the adhesive layer, a commonly known material can be used. For example, a thermosetting resin composition or a photocurable resin composition can be used. In this case, the thermosetting resin composition or the photocurable resin composition can be polymerized and cured by supplying energy thereto afterwards.

[0140] The adhesive layer may be a layer called a pressure-sensitive adhesive (PSA), which is attached to an object by pressing. The pressure-sensitive adhesive may be a pressure-sensitive adhesive that is "a substance that has adhesiveness at room temperature and adheres to an adherend with light pressure" (JIS K 6800), or it may be a capsule-type adhesive that is "an adhesive that contains a specific component in a protective film (microcapsules) and can maintain stability until the film is destroyed by an appropriate means (pressure, heat, etc.)" (JIS K 6800).

[0141] The hue adjustment layer is a layer having a function of adjusting the hue, and can adjust the hue of the optical film to a desired hue. The hue adjustment layer is, for example, a layer containing a resin and a colorant. Examples of the colorant include inorganic pigments such as titanium oxide, zinc oxide, red iron oxide, titanium oxide-based calcined pigments, ultramarine, cobalt aluminate, and carbon black; organic pigments such as azo compounds, quinacridone compounds, anthraquinone compounds, perylene compounds, isoindolinone compounds, phthalocyanine compounds, quinophthalone compounds, threne compounds, and diketopyrrolopyrrole compounds; extender pigments such as barium sulfate and calcium carbonate; and dyes such as basic dyes, acid dyes, and mordant dyes.

[0142] The refractive index adjusting layer is a layer having a function of adjusting the refractive index, and has a refractive index different from that of a single-layer optical film, and can impart a predetermined refractive index to the optical film. The refractive index adjusting layer may be, for example, a resin layer containing an appropriately selected resin and, if necessary, a pigment, or may be a thin metal film. Examples of pigments for adjusting the refractive index include silicon oxide, aluminum oxide, antimony oxide, tin oxide, titanium oxide, zirconium oxide, and tantalum oxide. The average primary particle diameter of the pigment may be 0.1 μm or less. By setting the average primary particle diameter of the pigment to 0.1 μm or less, diffuse reflection of light passing through the refractive index adjusting layer can be prevented, and a decrease in transparency can be prevented. Examples of metals used in the refractive index adjusting layer include metal oxides or metal nitrides such as titanium oxide, tantalum oxide, zirconium oxide, zinc oxide, tin oxide, silicon oxide, indium oxide, titanium oxynitride, titanium nitride, silicon oxynitride, and silicon nitride.

[0143] In one embodiment of the present invention, the optical film may have a protective film on at least one side (one side or both sides). For example, when the optical film has a functional layer on one side, the protective film may be laminated on the surface on the optical film side or the surface on the functional layer side, or may be laminated on both the optical film side and the functional layer side. When the optical film has a functional layer on both sides, the protective film may be laminated on the surface on one of the functional layers side, or may be laminated on the surfaces on both functional layers side. The protective film is a film for temporarily protecting the surface of the optical film or the functional layer, and is not particularly limited as long as it is a peelable film that can protect the surface of the optical film or the functional layer. Examples of the protective film include polyester-based resin films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin-based resin films such as polyethylene and polypropylene films, and acrylic resin films, and are preferably selected from the group consisting of polyolefin-based resin films, polyethylene terephthalate-based resin films, and acrylic resin films. When the optical film has two protective films, each protective film may be the same or different.

[0144] The thickness of the protective film is not particularly limited, but is usually 10 to 120 μm, preferably 15 to 110 μm, and more preferably 20 to 100 μm. When the optical film has two protective films, the thicknesses of the protective films may be the same or different.

[0145] [Method for producing optical film] The optical film of the present invention can be produced, but is not limited to, by the following process, for example: (a) preparing a liquid containing the polyimide-based resin (sometimes referred to as a resin varnish) (varnish preparation step); (b) a step of applying a resin varnish to a substrate to form a coating film (a coating step); and (c) A process of drying the applied liquid (coating film) to form an optical film (optical film formation process). The composition can be produced by a method comprising the steps of:

[0146] In the varnish preparation step, the polyimide resin is dissolved in a solvent, and the additives are added as necessary, followed by stirring and mixing to prepare a resin varnish.

[0147] The solvent used in preparing the resin varnish is not particularly limited as long as it can dissolve the resin. Examples of such solvents include amide-based solvents such as DMAc and DMF; lactone-based solvents such as γ-butyrolactone and γ-valerolactone; sulfur-containing solvents such as dimethylsulfone, dimethylsulfoxide, and sulfolane; carbonate-based solvents such as ethylene carbonate and propylene carbonate; and combinations thereof. Among these, amide-based solvents or lactone-based solvents are preferred. These solvents can be used alone or in combination of two or more. The resin varnish may also contain water, alcohol-based solvents, ketone-based solvents, acyclic ester-based solvents, ether-based solvents, and the like. The solid content concentration of the varnish is preferably 1 to 25% by mass, more preferably 5 to 15% by mass. In this specification, the solid content of the varnish refers to the total amount of components excluding the solvent from the varnish.

[0148] In the coating step, the varnish is applied onto the substrate to form a coating film by a known coating method, such as a wire bar coating method, a roll coating method such as reverse coating or gravure coating, a die coating method, a comma coating method, a lip coating method, a spin coating method, a screen coating method, a fountain coating method, a dipping method, a spray method, a drip molding method, etc.

[0149] In the optical film forming process, the coating film is dried and peeled off from the substrate to form an optical film. A drying process for drying the optical film may be performed after peeling. The coating film can be dried at a temperature of usually 50 to 350°C, preferably 50 to 230°C. In a preferred embodiment of the present invention, it is preferable to perform drying in stages. A varnish containing a high molecular weight resin tends to have a high viscosity, and it is generally difficult to obtain a uniform film, and it is difficult to obtain a film with excellent transparency. Therefore, by performing drying in stages, the varnish containing a high molecular weight resin can be dried uniformly. If necessary, the coating film may be dried under an inert atmosphere or reduced pressure. In addition, if the optical film is dried under vacuum conditions, fine air bubbles may be generated and remain in the film, which is a cause of reduced transparency, so it is preferable to perform drying under atmospheric pressure.

[0150] Examples of the substrate include a PET film, a PEN film, other polyimide-based resin or polyamide-based resin films, etc. Among them, from the viewpoint of excellent heat resistance, a PET film, a PEN film, etc. are preferred, and further, from the viewpoint of adhesion to the optical film and cost, a PET film is more preferred.

[0151] The optical film of the present invention can be suitably used as a front plate (sometimes called a window film) of a display device, particularly a flexible display device, particularly a front plate of a rollable display or a foldable display. That is, the optical film of the present invention is preferably a film for a front plate of a flexible display device. The front plate has a function of protecting the display element of the flexible display device. The flexible display device is a display device used with operations such as repeatedly folding and rolling the image display device. The front plate of a flexible display device used with such repeated folding operations is required to have high bending resistance, particularly high folding resistance. In addition, the front plate is also required to have high visibility. Compared with a film for a substrate of an image display device used inside the image display device, the front plate of an image display device, particularly a film for a front plate of a flexible display device, is required to have high visibility and high bending resistance. For example, the film of the present invention preferably has the total light transmittance, haze and / or YI value described above from the viewpoint of easily improving visibility when used as a front panel of a flexible display device, and preferably satisfies the number of folding times in the MIT folding fatigue test described above from the viewpoint of easily improving bending resistance, particularly folding resistance, when used as a front panel of a flexible display device. Examples of display devices include televisions, smartphones, mobile phones, car navigation systems, tablet PCs, portable game consoles, electronic paper, indicators, bulletin boards, watches, and wearable devices such as smart watches. Examples of flexible displays include display devices having flexible characteristics, such as televisions, smartphones, mobile phones, and smart watches. Examples of flexible display devices include all image display devices having flexible characteristics, such as the above-mentioned rollable displays and foldable displays. A rollable display is an image display device in which an image display portion including a front panel is wound up in a roll, and the image display portion is pulled out and used in a flat or curved state, and an operation such as winding up into a roll is performed every time it is used.A foldable display is an image display device in which an image display portion including a front panel is folded and the image display portion is opened to be flat or curved for use, and the image display device is folded or otherwise manipulated each time it is used. Such an image display device in which operations such as rolling up and folding are repeatedly performed is called a flexible image display device.

[0152] [Flexible display device] The present invention also provides a flexible display device comprising the optical film of the present invention. The optical film of the present invention is preferably used as a front plate in a flexible display device, and the front plate may be called a window film. The flexible display device comprises a laminate for a flexible display device and an organic EL display panel, and the laminate for a flexible display device is disposed on the viewing side of the organic EL display panel and is configured to be foldable. The laminate for a flexible display device may further contain a polarizing plate and a touch sensor, and although the order of lamination of these is arbitrary, it is preferable that the laminate is laminated in the order of a window film, a polarizing plate, a touch sensor, or a window film, a touch sensor, and a polarizing plate from the viewing side. If a polarizing plate is present on the viewing side of the touch sensor, the pattern of the touch sensor is less visible, and the visibility of the displayed image is improved, which is preferable. Each member can be laminated using an adhesive, a pressure-sensitive adhesive, or the like. In addition, a light-shielding pattern formed on at least one surface of any of the layers of the window film, the polarizing plate, and the touch sensor can be provided.

[0153] <Polarizing plate> As described above, the flexible display device of the present invention preferably further comprises a polarizing plate, particularly a circular polarizing plate. The circular polarizing plate is a functional layer having a function of transmitting only right-handed or left-handed circularly polarized components by laminating a λ / 4 retardation plate on a linear polarizing plate. For example, the circular polarizing plate is used to convert external light into right-handed circularly polarized light, block the external light that is reflected by the organic EL panel and becomes left-handed circularly polarized light, and transmit only the light-emitting component of the organic EL, thereby suppressing the influence of reflected light and making the image easier to see. In order to achieve the circular polarization function, the absorption axis of the linear polarizing plate and the slow axis of the λ / 4 retardation plate theoretically need to be 45°, but in practice, it is 45±10°. The linear polarizing plate and the λ / 4 retardation plate do not necessarily need to be laminated adjacent to each other, and it is sufficient that the relationship between the absorption axis and the slow axis satisfies the above-mentioned range. It is preferable to achieve complete circular polarization at all wavelengths, but this is not necessarily required in practice, so the circular polarizing plate in the present invention also includes an elliptical polarizing plate. It is also preferable to further laminate a λ / 4 phase difference film on the viewing side of the linear polarizing plate to make the emitted light circularly polarized, thereby improving visibility when wearing polarized sunglasses.

[0154] A linear polarizing plate is a functional layer that transmits light vibrating in the transmission axis direction but blocks polarized light of vibration components perpendicular thereto. The linear polarizing plate may be a linear polarizer alone or a linear polarizer with a protective film attached to at least one surface of the linear polarizer. The thickness of the linear polarizing plate may be 200 μm or less, and is preferably 0.5 to 100 μm. When the thickness of the linear polarizing plate is within the above range, the flexibility of the linear polarizing plate tends not to decrease.

[0155] The linear polarizer may be a film-type polarizer produced by dyeing and stretching a polyvinyl alcohol (hereinafter sometimes abbreviated as PVA)-based film. A dichroic dye such as iodine is adsorbed to the PVA-based film oriented by stretching, or the dichroic dye is oriented by stretching in a state where it is adsorbed to PVA, and the film exhibits polarization performance. The production of the film-type polarizer may further include steps such as swelling, crosslinking with boric acid, washing with an aqueous solution, and drying. The stretching and dyeing steps may be performed on the PVA-based film alone, or may be performed in a state where it is laminated with another film such as polyethylene terephthalate. The thickness of the PVA-based film used is preferably 10 to 100 μm, and the stretching ratio is preferably 2 to 10 times. Another example of the polarizer is a liquid crystal coating type polarizer formed by coating a liquid crystal polarizing composition. The liquid crystal polarizing composition may contain a liquid crystal compound and a dichroic dye compound. The liquid crystal compound may have a property of exhibiting a liquid crystal state, and is preferably in a highly oriented state such as a smectic phase, since it can exhibit high polarization performance. The liquid crystal compound preferably has a polymerizable functional group. The dichroic dye compound is a dye that exhibits dichroism when aligned together with the liquid crystal compound, and may have a polymerizable functional group, or the dichroic dye itself may have liquid crystal properties. Any of the compounds contained in the liquid crystal polarizing composition has a polymerizable functional group. The liquid crystal polarizing composition may further include an initiator, a solvent, a dispersant, a leveling agent, a stabilizer, a surfactant, a crosslinking agent, a silane coupling agent, etc. The liquid crystal polarizing layer is produced by applying a liquid crystal polarizing composition onto an alignment film to form a liquid crystal polarizing layer. The liquid crystal polarizing layer can be formed to have a smaller thickness than a film-type polarizer, and the thickness is preferably 0.5 to 10 μm, more preferably 1 to 5 μm.

[0156] The alignment film is produced, for example, by applying an alignment film-forming composition onto a substrate and imparting alignment by rubbing, polarized light irradiation, or the like. The alignment film-forming composition contains an alignment agent, and may further contain a solvent, a crosslinking agent, an initiator, a dispersant, a leveling agent, a silane coupling agent, or the like. Examples of the alignment agent include polyvinyl alcohols, polyacrylates, polyamic acids, and polyimides. When using an alignment agent that imparts alignment by polarized light irradiation, it is preferable to use an alignment agent that contains a cinnamate group. The Mw of the polymer used as the alignment agent is, for example, about 10,000 to 1,000,000. The thickness of the alignment film is preferably 5 to 10,000 nm, and more preferably 10 to 500 nm in terms of sufficient expression of alignment control force. The liquid crystal polarizing layer can be peeled off from the substrate and transferred to the substrate, or the substrate can be directly laminated. It is also preferable that the substrate serves as a transparent substrate for a protective film, a retardation plate, or a window film.

[0157] The protective film may be a transparent polymer film, and may be the same as the materials and additives used in the transparent substrate of the window film. The protective film may also be a coating type protective film obtained by applying and curing a cationic curing composition such as an epoxy resin or a radical curing composition such as an acrylate. The protective film may contain a plasticizer, an ultraviolet absorber, an infrared absorber, a colorant such as a pigment or dye, a fluorescent whitening agent, a dispersant, a heat stabilizer, a light stabilizer, an antistatic agent, an antioxidant, a lubricant, a solvent, etc., as necessary. The thickness of the protective film is preferably 200 μm or less, more preferably 1 to 100 μm. When the thickness of the protective film is within the above range, the flexibility of the film tends not to decrease.

[0158] The λ / 4 retardation plate is a film that gives a phase difference of λ / 4 in a direction perpendicular to the traveling direction of incident light (in-plane direction of the film). The λ / 4 retardation plate may be a stretched retardation plate manufactured by stretching a polymer film such as a cellulose film, an olefin film, or a polycarbonate film. The λ / 4 retardation plate may contain a retardation regulator, a plasticizer, an ultraviolet absorber, an infrared absorber, a colorant such as a pigment or a dye, a fluorescent whitening agent, a dispersant, a heat stabilizer, a light stabilizer, an antistatic agent, an antioxidant, a lubricant, a solvent, etc., as necessary. The thickness of the stretched retardation plate is preferably 200 μm or less, more preferably 1 to 100 μm. When the thickness of the stretched retardation plate is in the above range, the flexibility of the stretched retardation plate tends not to decrease. Another example of the λ / 4 retardation plate is a liquid crystal coating type retardation plate formed by coating a liquid crystal composition. The liquid crystal composition contains a liquid crystal compound that exhibits a liquid crystal state such as nematic, cholesteric, smectic, etc. The liquid crystal compound has a polymerizable functional group. The liquid crystal composition may further include an initiator, a solvent, a dispersant, a leveling agent, a stabilizer, a surfactant, a crosslinking agent, a silane coupling agent, and the like. The liquid crystal coating type retardation plate can be produced by coating a liquid crystal composition on a base and curing it to form a liquid crystal retardation layer, similar to the liquid crystal polarizing layer. The liquid crystal coating type retardation plate can be formed thinner than the stretching type retardation plate. The thickness of the liquid crystal polarizing layer is preferably 0.5 to 10 μm, more preferably 1 to 5 μm. The liquid crystal-coated retardation plate can be peeled off from the substrate and transferred to the substrate, or the substrate can be directly laminated. It is also preferable that the substrate serves as a transparent substrate for a protective film, a retardation plate, or a window film.

[0159] Generally, there are many materials that exhibit larger birefringence at shorter wavelengths and smaller birefringence at longer wavelengths. In this case, since it is not possible to achieve a phase difference of λ / 4 in the entire visible light region, the in-plane phase difference is designed to be preferably 100 to 180 nm, more preferably 130 to 150 nm, so that it is λ / 4 around 560 nm where visibility is high. A reverse dispersion λ / 4 phase difference plate using a material having a birefringence wavelength dispersion characteristic reverse to that of normal is preferable in terms of good visibility. As such materials, for example, those described in JP-A-2007-232873 and JP-A-2010-30979 can be used as stretched phase difference plates and liquid crystal coating phase difference plates, respectively. As another method, a technique is known in which a wideband λ / 4 retardation plate is obtained by combining it with a λ / 2 retardation plate (for example, JP-A-10-90521). The λ / 2 retardation plate is also manufactured using the same materials and methods as the λ / 4 retardation plate. The combination of the stretched retardation plate and the liquid crystal coating retardation plate is arbitrary, but the thickness of either can be reduced by using the liquid crystal coating retardation plate. A method of laminating a positive C plate on the circularly polarizing plate to improve visibility in oblique directions is known (for example, JP 2014-224837 A, etc.). The positive C plate may be a liquid crystal coating type retardation plate or a stretched type retardation plate. The retardation in the thickness direction of the retardation plate is preferably -200 to -20 nm, more preferably -140 to -40 nm.

[0160] [Touch sensor] As described above, the flexible display device of the present invention preferably further includes a touch sensor. The touch sensor is used as an input means. As the touch sensor, various types such as a resistive film type, a surface acoustic wave type, an infrared type, an electromagnetic induction type, and a capacitance type can be mentioned, and a capacitance type is preferably mentioned. The capacitive touch sensor is divided into an active area and a non-active area located on the periphery of the active area. The active area corresponds to an area (display area) where a screen is displayed on a display panel and is an area where a user's touch is sensed, and the non-active area corresponds to an area (non-display area) where a screen is not displayed on a display device. The touch sensor may include a substrate having a flexible characteristic, a sensing pattern formed in the active area of ​​the substrate, and sensing lines formed in the non-active area of ​​the substrate for connecting to an external driving circuit via the sensing pattern and a pad part. The substrate having a flexible characteristic may be made of the same material as the transparent substrate of the window film.

[0161] The sensing pattern may include a first pattern formed in a first direction and a second pattern formed in a second direction. The first pattern and the second pattern are arranged in different directions. The first pattern and the second pattern are formed in the same layer, and in order to sense a touch point, the first pattern and the second pattern must be electrically connected to each other. The first pattern is a form in which a plurality of unit patterns are connected to each other through joints, but the second pattern is a structure in which a plurality of unit patterns are separated from each other in an island form, so a separate bridge electrode is required to electrically connect the second pattern. A well-known transparent electrode may be applied to the electrode for connecting the second pattern. Examples of materials for the transparent electrode include indium tin oxide (ITO), indium zinc oxide (IZO), zinc oxide (ZnO), indium zinc tin oxide (IZTO), indium gallium zinc oxide (IGZO), cadmium tin oxide (CTO), PEDOT (poly(3,4-ethylenedioxythiophene)), carbon nanotubes (CNT), graphene, and metal wires, and preferably ITO. These may be used alone or in combination of two or more. There are no particular limitations on the metal used for the metal wire, and examples thereof include silver, gold, aluminum, copper, iron, nickel, titanium, selenium, and chromium, which may be used alone or in combination of two or more. The bridge electrode may be formed on an insulating layer on the sensing pattern, or the bridge electrode may be formed on a substrate, and an insulating layer and a sensing pattern may be formed thereon. The bridge electrode may be made of the same material as the sensing pattern, or may be made of molybdenum, silver, aluminum, copper, palladium, gold, platinum, zinc, tin, titanium, or an alloy of two or more of these materials. Since the first pattern and the second pattern must be electrically insulated, an insulating layer is formed between the sensing pattern and the bridge electrode. The insulating layer can be formed only between the joint of the first pattern and the bridge electrode, or can be formed as a layer covering the entire sensing pattern. In the case of a layer covering the entire sensing pattern, the bridge electrode can connect the second pattern through a contact hole formed in the insulating layer.

[0162] The touch sensor may further include an optical adjustment layer between the substrate and the electrode as a means for appropriately compensating for a difference in transmittance between a patterned region where a sensing pattern is formed and a non-patterned region where a sensing pattern is not formed, specifically, a difference in light transmittance caused by a difference in refractive index between these regions. The optical adjustment layer may include an inorganic insulating material or an organic insulating material. The optical adjustment layer may be formed by coating a photocurable composition including a photocurable organic binder and a solvent on the substrate. The photocurable composition may further include inorganic particles. The inorganic particles may increase the refractive index of the optical adjustment layer. The photocurable organic binder may contain, within the scope not impairing the effects of the present invention, a copolymer of each monomer, such as an acrylate monomer, a styrene monomer, a carboxylic acid monomer, etc. The photocurable organic binder may be, for example, a copolymer containing different repeating units, such as an epoxy group-containing repeating unit, an acrylate repeating unit, a carboxylic acid repeating unit, etc. Examples of the inorganic particles include zirconia particles, titania particles, and alumina particles. The photocurable composition may further include various additives such as a photopolymerization initiator, a polymerizable monomer, and a curing assistant.

[0163] [Adhesive layer] Each layer (window film, circular polarizer, touch sensor) constituting the laminate for flexible display devices and the film members (linear polarizer, λ / 4 retardation plate, etc.) constituting each layer can be bonded by an adhesive. As the adhesive, a water-based adhesive, an organic solvent-based adhesive, a solvent-free adhesive, a solid adhesive, a solvent-volatile adhesive, a water-based solvent-volatile adhesive, a moisture-curing adhesive, a heat-curing adhesive, an anaerobic curing adhesive, an active energy ray-curing adhesive, a curing agent mixed adhesive, a hot melt adhesive, a pressure-sensitive adhesive (adhesive), a re-moistening adhesive, etc., which are commonly used, can be used, and preferably a water-based solvent-volatile adhesive, an active energy ray-curing adhesive, or an adhesive can be used. The thickness of the adhesive layer can be appropriately adjusted according to the required adhesive strength, etc., and is preferably 0.01 to 500 μm, more preferably 0.1 to 300 μm. The laminate for flexible display devices has a plurality of adhesive layers, and the thickness and type of each of them may be the same or different.

[0164] As the aqueous solvent volatilizing adhesive, a water-dispersed polymer such as a polyvinyl alcohol polymer, a water-soluble polymer such as starch, an ethylene-vinyl acetate emulsion, or a styrene-butadiene emulsion can be used as a base polymer. In addition to the base polymer and water, a crosslinking agent, a silane compound, an ionic compound, a crosslinking catalyst, an antioxidant, a dye, a pigment, an inorganic filler, an organic solvent, or the like may be blended. When bonding is performed using the aqueous solvent volatilizing adhesive, the aqueous solvent volatilizing adhesive is injected between the adherend layers, the adherend layers are laminated, and then the layers are dried to impart adhesiveness. When the aqueous solvent volatilizing adhesive is used, the thickness of the adhesive layer is preferably 0.01 to 10 μm, more preferably 0.1 to 1 μm. When the aqueous solvent volatilizing adhesive is used in a plurality of layers, the thickness and type of each layer may be the same or different.

[0165] The active energy ray curable adhesive can be formed by curing an active energy ray curable composition containing a reactive material that forms an adhesive layer by irradiating active energy rays. The active energy ray curable composition can contain at least one polymer of a radical polymerizable compound and a cationic polymerizable compound similar to those contained in the hard coat composition. The radical polymerizable compound can be the same compound as the radical polymerizable compound in the hard coat composition. The cationically polymerizable compound may be the same as the cationically polymerizable compound in the hard coat composition. The cationic polymerizable compound used in the active energy ray curable composition is preferably an epoxy compound. It is also preferable that the adhesive composition contains a monofunctional compound as a reactive diluent in order to reduce the viscosity of the adhesive composition.

[0166] The active energy ray composition may contain a monofunctional compound to reduce viscosity. Examples of the monofunctional compound include an acrylate monomer having one (meth)acryloyl group in one molecule, and a compound having one epoxy group or oxetanyl group in one molecule, such as glycidyl (meth)acrylate. The active energy ray composition may further contain a polymerization initiator. The polymerization initiator may include a radical polymerization initiator, a cationic polymerization initiator, a radical and cationic polymerization initiator, etc., and these may be appropriately selected and used. These polymerization initiators are decomposed by at least one of active energy ray irradiation and heating, generating radicals or cations to advance radical polymerization and cationic polymerization. In the description of the hard coat composition, an initiator that can initiate at least one of radical polymerization and cationic polymerization by active energy ray irradiation may be used. The active energy ray curable composition may further contain an ion scavenger, an antioxidant, a chain transfer agent, an adhesion imparting agent, a thermoplastic resin, a filler, a flow viscosity modifier, a plasticizer, an antifoaming agent, an additive, and a solvent. When two adherend layers are bonded by the active energy ray curable adhesive, the active energy ray curable composition is applied to either or both of the adherend layers, and then the layers are laminated together, and either or both of the adherend layers are irradiated with active energy rays to cure the layers, thereby bonding the layers together. When the active energy ray curable adhesive is used, the thickness of the adhesive layer is preferably 0.01 to 20 μm, more preferably 0.1 to 10 μm. When the active energy ray curable adhesive is used to form a plurality of adhesive layers, the thickness and type of each layer may be the same or different.

[0167] The adhesive is classified into acrylic adhesives, urethane adhesives, rubber adhesives, silicone adhesives, etc. according to the base polymer, and any of them can be used. In addition to the base polymer, the adhesive may contain a crosslinking agent, a silane compound, an ionic compound, a crosslinking catalyst, an antioxidant, a tackifier, a plasticizer, a dye, a pigment, an inorganic filler, etc. The components constituting the adhesive are dissolved and dispersed in a solvent to obtain an adhesive composition, and the adhesive composition is applied to a substrate and then dried to form an adhesive layer. The adhesive layer may be formed directly, or a layer formed separately on a substrate may be transferred. It is also preferable to use a release film to cover the adhesive surface before adhesion. When the active energy ray curable adhesive is used, the thickness of the adhesive layer is preferably 0.1 to 500 μm, more preferably 1 to 300 μm. When a plurality of layers of the adhesive are used, the thickness and type of each layer may be the same or different.

[0168] [Light blocking pattern] The light-shielding pattern can be applied as at least a part of a bezel or a housing of the flexible display device. The light-shielding pattern hides wiring arranged at the edge of the flexible display device, making it difficult to see, thereby improving the visibility of an image. The light-shielding pattern may be in the form of a single layer or multiple layers. The color of the light-shielding pattern is not particularly limited, and may be various colors such as black, white, and metallic colors. The light-shielding pattern may be formed of a pigment for realizing a color and a polymer such as an acrylic resin, an ester resin, an epoxy resin, a polyurethane, or a silicone. These may be used alone or in a mixture of two or more kinds. The light-shielding pattern may be formed by various methods such as printing, lithography, and inkjet. The thickness of the light-shielding pattern is preferably 1 to 100 μm, more preferably 2 to 50 μm. It is also preferable to impart a shape such as a slope in the thickness direction of the light-shielding pattern. EXAMPLES

[0169] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" mean "% by mass" and "parts by mass" unless otherwise specified. First, the evaluation methods will be described.

[0170] <Measurement of strength> The yield strength of the optical films obtained in the examples and comparative examples was measured using "Autograph AG-IS" manufactured by Shimadzu Corporation. A film measuring 10 mm in length and width was prepared, and the stress-strain curve (SS curve) was measured under the conditions of a chuck distance of 50 mm and a pulling speed of 10 mm / min. 1. Data organization of SS curve Ten consecutive points are sampled from the measurement start point on the SS curve, and fitted to a quadratic function using the least squares method. Then, one point is removed from the left side of the measurement start point and one point is added to the right side until the quadratic function fitting of the 10 sampling points results in an upward convex shape. Data reduction is completed when the fitting function becomes upward convex. 2. Calculating the tangent equation of the SS curve 1. For the data from the \(n = i\) -th to \(j\) -th data (\(j = 2\sim50\)) of the data in 1, the slope and intercept are obtained by the least - squares method. Then, for the \(j - 1\) slopes, the data from the \(k\) -th (\(k = 1\sim48\)) to the 49 -th data are fitted to a linear function by the least - squares method, and the slope when the strain is 0 is obtained by extrapolation. The median value of the 48 points obtained is taken and defined as the slope of the straight line (tangent of the S - S curve) when the strain is 0. The intercept is calculated in the same way to obtain the equation of the tangent of the S - S curve at a strain of 0. 3. Calculation of endurance 2. The tangent of the S - S curve obtained in 2 at a strain of 0 is translated parallel to the strain direction by 0.2%. The stress value of the data whose measured stress data exceeds the stress of the translated straight line is defined as the endurance.

[0171] <Total light transmittance> In accordance with JIS K 7105:1981, the total light transmittance (\(Tt\)) of the optical films obtained in the examples and comparative examples was measured using a fully automatic direct - reading haze computer HGM - 2DP manufactured by Suga Test Instruments Co., Ltd.

[0172] <Haze> In accordance with JIS K 7105:1981, the optical films obtained in the examples and comparative examples were cut into a size of 30 mm×30 mm and measured using a fully automatic direct - reading haze computer HGM - 2DP manufactured by Suga Test Instruments Co., Ltd.

[0173] <YI value> For the optical films obtained in the examples and comparative examples, the tristimulus values (\(X\), \(Y\), \(Z\)) were determined using an ultraviolet - visible - near - infrared spectrophotometer (V - 670 manufactured by JASCO Corporation), and the YI value was calculated by substituting them into the following calculation formula. YI = 100×(1.2769X - 1.0592Z) / Y

[0174] <Elastic modulus> The elastic modulus of the optical films obtained in the examples and comparative examples was measured using an "Autograph AG - IS" manufactured by Shimadzu Corporation. A film with a width of 10 mm in both length and width was prepared, and the stress - strain curve (S - S curve) was measured under the conditions of a chuck - to - chuck distance of 50 mm and a tensile speed of 10 mm / min, and the elastic modulus was calculated from its slope.

[0175] <Evaluation of folding resistance> In accordance with ASTM standard D2176-16, the number of folding cycles of the optical films in the examples and comparative examples was determined as follows. The optical film was cut into strips of 15 mm×100 mm using a dumbbell cutter. The cut optical film was set on the main body of an MIT folding fatigue tester (Model 0530, manufactured by Toyo Seiki Seisakusho Co., Ltd.), and the number of reciprocating folding cycles in the front and back directions until the optical film broke was measured under the conditions of a test speed of 175 cpm, a folding angle of 135°, a load of 0.75 kgf, and a radius R = 1 mm of the folding clamp. This was defined as the number of folding cycles (also referred to as the folding resistance).

[0176] <Measurement of thickness> The thickness of the optical films obtained in the examples and comparative examples was measured using an ABS digital indicator (manufactured by Mitutoyo Corporation, "ID-C112BS").

[0177] <Measurement of Mw> GPC measurement (1) Pretreatment method DMF eluent (10 mmol / L lithium bromide addition solution) was added to the polyamide-imide resins obtained in the examples and comparative examples so that the concentration became 2 mg / mL, and the mixture was heated with stirring at 80°C for 30 minutes. After cooling, the solution filtered through a 0.45 μm membrane filter was used as the measurement solution. (2) Measurement conditions Column: TSKgel α-2500 (7.8 mm diameter×300 mm)×1 column, α-M (13) 7.8 mm diameter×300 mm)×2 columns, manufactured by Tosoh Corporation Eluent: DMF (with 10 mmol / L lithium bromide added) Flow rate: 1.0 mL / min Detector: RI detector Column temperature: 40°C Injection volume: 100 μL Molecular weight standard: Standard polystyrene

[0178] <Synthesis Example 1: Production of polyamide-imide resin (1)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.13 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TAHMBP were added to the flask so that each was 20.20 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added to 27.27 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added to 27.27 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added to 6.06 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 60.61 mol%, 60.61 mol%, and 282.83 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. The internal temperature was then raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature, and the reaction solution was poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (1). The Mw of the resulting polyamideimide resin (1) was 748,000.

[0179] <Synthesis Example 2: Production of polyamideimide resin (2)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.27 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and an ester of trimellitic anhydride and 4,4'-biphenol were added to the flask so that each was 20.10 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added to 27.14 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added to 27.14 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added to 6.03 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 60.30 mol%, 60.30 mol%, and 281.41 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. The internal temperature was then raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (2). The Mw of the obtained polyamideimide resin (2) was 139,000.

[0180] <Synthesis Example 3: Production of polyamideimide resin (3)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.35 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that the solid content was 41.24 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added so that the solid content was 27.84 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added so that the solid content was 27.84 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added so that the solid content was 6.19 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 61.86 mol%, 61.86 mol%, and 288.66 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. After that, the internal temperature was raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (3). The Mw of the obtained polyamideimide resin (3) was 174,000.

[0181] <Synthesis Example 5: Production of polyamideimide resin (5)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.81 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that the solid content was 20.41 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added so that the solid content was 36.73 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added so that the solid content was 36.73 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added so that the solid content was 8.16 mol% relative to TFMB, and the mixture was stirred for 2 hours, but the viscosity increased significantly during the process and the solution became agar-like. Since the subsequent synthesis operations became difficult, the resin synthesis was abandoned.

[0182] <Synthesis Example 6: Production of polyamideimide resin (6)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.44 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that it was 30.15 mol% relative to TFMB, and stirred at room temperature for 16 hours. After cooling to 10°C, OMTPC was added so that it was 33.08 mol% relative to TFMB, and after stirring for 10 minutes, OMTPC was further added so that it was 33.08 mol% relative to TFMB, and stirred for 30 minutes. Then, the same amount of DMAc as the initially added DMAc was added, and after stirring for 10 minutes, OMTPC was added so that it was 7.04 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 70.35 mol%, 70.35 mol%, and 211.06 mol% relative to TFMB, respectively, and the mixture was stirred for 30 minutes. After that, the internal temperature was raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (6). The Mw of the obtained polyamideimide resin (6) was 612,000.

[0183] <Synthesis Example 7: Production of polyamideimide resin (7)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.63 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that it was 20.20 mol% relative to TFMB, and stirred at room temperature for 16 hours. After cooling to 10°C, DMTPC was added so that it was 36.36 mol% relative to TFMB, and after stirring for 10 minutes, DMTPC was further added so that it was 36.36 mol% relative to TFMB, and stirred for 30 minutes. Then, the same amount of DMAc as the initially added DMAc was added, and after stirring for 10 minutes, DMTPC was added so that it was 8.08 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 80.81 mol%, 80.81 mol%, and 141.41 mol% relative to TFMB, respectively, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature and poured into a large amount of methanol in the form of filaments, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (7). The Mw of the resulting polyamideimide resin (7) was 482,000.

[0184] <Synthesis Example 8: Production of polyamideimide resin (8)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.63 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that it was 20.10 mol% relative to TFMB, and stirred at room temperature for 16 hours. After cooling to 10°C, OMTPC was added so that it was 36.18 mol% relative to TFMB, and after stirring for 10 minutes, OMTPC was further added so that it was 36.18 mol% relative to TFMB, and stirred for 30 minutes. Then, the same amount of DMAc as the initially added DMAc was added, and after stirring for 10 minutes, OMTPC was added so that it was 8.04 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 80.40 mol%, 80.40 mol%, and 140.70 mol% relative to TFMB, respectively, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature and poured into a large amount of methanol in the form of filaments, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (8). The Mw of the resulting polyamideimide resin (8) was 483,000.

[0185] <Synthesis Example 9: Production of polyamideimide resin (9)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.52 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and BPDA were added to the flask so that each was 20.10 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, OMTPC was added to TFMB so that it was 27.14 mol% relative to TFMB, and after stirring for 10 minutes, OMTPC was further added to TFMB so that it was 27.14 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as the first addition was added, and after stirring for 10 minutes, OMTPC was added to TFMB so that it was 6.03 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 60.30 mol%, 60.30 mol%, and 281.41 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. The internal temperature was then raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (9). The Mw of the obtained polyamide-based resin (9) was 594,000.

[0186] <Synthesis Example 10: Production of polyamideimide resin (10)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.08 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TAHMBP were added to the flask so that each was 20.62 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added to 27.84 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added to 27.84 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as the first addition was added, and after stirring for 10 minutes, TPC was added to 6.19 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 61.86 mol%, 61.86 mol%, and 288.66 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. After that, the internal temperature was raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature, and the reaction solution was poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (10). The Mw of the resulting polyamideimide resin (10) was 486,000.

[0187] <Synthesis Example 11: Production of polyamideimide resin (11)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.08 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TAHMBP were added to the flask so that each was 20.62 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added to 27.84 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added to 27.84 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added to 6.19 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 61.86 mol%, 61.86 mol%, and 288.66 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. After that, the internal temperature was raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature, and the reaction solution was poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (11). The Mw of the resulting polyamideimide resin (11) was 215,000.

[0188] <Synthesis Example 12: Production of polyamideimide resin (12)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.16 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, TAHMBP was added to the flask so that the solid content was 30.61 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added so that the solid content was 32.14 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added so that the solid content was 32.14 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added so that the solid content was 7.14 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 71.43 mol%, 71.43 mol%, and 214.29 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. The internal temperature was then raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature, and the reaction solution was poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (12). The Mw of the resulting polyamideimide resin (12) was 764,000.

[0189] <Synthesis Example 13: Production of polyamideimide resin (13)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 4.86 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, TAHMBP was added so that the solid content was 40.82 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added so that the solid content was 27.55 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added so that the solid content was 27.55 mol% relative to TFMB, and the mixture was stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added so that the solid content was 6.12 mol% relative to TFMB, and the mixture was stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 61.22 mol%, 61.22 mol%, and 285.71 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. After that, the internal temperature was raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature, and the reaction solution was poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (13). The Mw of the resulting polyamideimide resin (13) was 613,000.

[0190] <Synthesis Example 14: Production of polyamideimide resin (14)> In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.29 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TAHMBP were added to the flask so that the solid content was 10.20 mol% and 20.41 mol% relative to TFMB, respectively, and stirred at room temperature for 16 hours. After cooling to 10°C, TPC was added to 32.14 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added to 32.14 mol% relative to TFMB and stirred for 30 minutes. Then, the same amount of DMAc as that added initially was added, and after stirring for 10 minutes, TPC was added to 7.14 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-picoline, and acetic anhydride were added to the flask so that the amounts were 71.43 mol%, 71.43 mol%, and 214.29 mol%, respectively, relative to TFMB, and the mixture was stirred for 30 minutes. The internal temperature was then raised to 70°C and the mixture was stirred for a further 3 hours to obtain a reaction liquid. The resulting reaction solution was cooled to room temperature, and the reaction solution was poured into a large amount of methanol in the form of a filament, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyamideimide resin (14). The Mw of the resulting polyamideimide resin (14) was 751,000.

[0191] <Example 1> The polyamideimide resin (1) obtained in Synthesis Example 1 and DMAc were mixed in such an amount that the content ratio of the polyamideimide resin in the resin composition was 10 mass%. The obtained resin composition was applied to the smooth surface of a polyester substrate (manufactured by Toyobo Co., Ltd., product name "A4100") using an applicator so that the thickness of the free-standing film was 55 μm, and the coating film was dried at 50° C. for 30 minutes and then at 140° C. for 15 minutes, and then peeled off from the polyester substrate to obtain a free-standing film. The free-standing film was fixed to a metal frame and further dried at 200° C. for 40 minutes in the atmosphere to obtain a polyamideimide resin film (1) having a thickness of 50 μm.

[0192] <Example 2> The polyamideimide resin (6) obtained in Synthesis Example 6 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (6) having a thickness of 38 μm.

[0193] <Example 3> The polyamideimide resin (7) obtained in Synthesis Example 7 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (7) having a thickness of 42 μm.

[0194] <Example 4> The polyamideimide resin (8) obtained in Synthesis Example 8 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (8) having a thickness of 40 μm.

[0195] <Example 5> The polyamideimide resin (9) obtained in Synthesis Example 9 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (9) having a thickness of 40 μm.

[0196] <Example 6> The polyamideimide resin (10) obtained in Synthesis Example 10 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (10) having a thickness of 40 μm.

[0197] <Example 7> The polyamideimide resin (11) obtained in Synthesis Example 11 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (11) having a thickness of 40 μm.

[0198] <Example 8> The polyamideimide resin (12) obtained in Synthesis Example 12 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (12) having a thickness of 40 μm.

[0199] <Example 9> The polyamideimide resin (13) obtained in Synthesis Example 13 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (13) having a thickness of 40 μm.

[0200] <Example 10> The polyamideimide resin (14) obtained in Synthesis Example 14 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (14) having a thickness of 40 μm.

[0201] <Comparative Example 1> The polyamideimide resin (2) obtained in Synthesis Example 2 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (2) having a thickness of 50 μm.

[0202] <Comparative Example 2> The polyamideimide resin (3) obtained in Synthesis Example 3 and DMAc were mixed in such amounts that the content of the polyamideimide resin in the resin composition was 10 mass %. The obtained resin composition was used in the same manner as in Example 1 to obtain a polyamideimide resin film (3) having a thickness of 50 μm.

[0203] The polyamideimide resin films of the Examples and Comparative Examples obtained as described above were subjected to measurements of yield strength, elastic modulus, total light transmittance, haze, YI value, and number of folding cycles. The results are shown in Tables 1 and 2. Note that the resin of Synthesis Example 5 became insoluble during synthesis, and a polyamideimide resin could not be synthesized, so measurements and evaluations could not be performed.

[0204] [Table 1]

[0205] [Table 2]

[0206] As shown in Tables 1 and 2, the optical films of Examples 1 to 10 were confirmed to have low YI values, high strength, and excellent folding resistance. They were also confirmed to have high transparency. In contrast, the optical films of Comparative Examples 1 and 2 were confirmed to have low strength and insufficient folding resistance.

Claims

1. An optical film containing a polyimide-based resin, the optical film having a proof stress of 81 MPa or more in a tensile test and a yellowness index of less than 3.0, wherein the optical film has an elastic modulus of 4.8 GPa or more, the polyimide-based resin has a weight average molecular weight of 100,000 or more, and the polyimide-based resin has a formula (1): 【Chemistry 1】 [In formula (1), Y represents a tetravalent organic group, X represents a divalent organic group, and * represents a bond.] wherein Y in formula (1) is a structural unit represented by formula (2): 【Chemistry 2】 [In formula (2), R 1 s each independently represent a halogen atom or an alkyl group, alkoxy group, aryl group, or aryloxy group which may have a halogen atom; R 2 to R 5 each independently represent a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom; m each independently represents an integer of 0 to 3; n represents an integer of 1 to 4; * represents a bond; and with the proviso that in at least one benzene ring having R 2 to R 5 , at least one of R 2 to R 5 is a monovalent hydrocarbon group which may have a halogen atom] An optical film comprising a structure represented by:

2. The optical film according to claim 1 , having a total light transmittance of 85% or more.

3. 3. The optical film according to claim 1, wherein the polyimide resin is a polyamide-imide resin.

4. The polyimide resin has the formula (3): 【Chemistry 3】 [In formula (3), Z and X each independently represent a divalent organic group, and * represents a bond.] The optical film according to any one of claims 1 to 3, comprising a structural unit represented by:

5. The polyimide resin is represented by the formula (4): 【Chemistry 4】 In formula (4), each W is independently a single bond, —O—, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, —SO 2 -, -S-, -CO-, -PO-, -PO 2 -, -N(R W1 )-or-Si(R W2 ) 2 - represents R W1 and R W2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 8 each independently represents a halogen atom, or an alkyl group, alkoxy group, aryl group, or aryloxy group which may have a halogen atom; each p independently represents an integer of 0 to 4; q represents an integer of 0 to 4; and * represents a bond. The optical film of claim 4 , comprising a structure represented by:

6. 6. The optical film according to claim 1, which is a film for a front panel of a flexible display device.

7. A flexible display device comprising the optical film according to any one of claims 1 to 6.

8. The flexible display of claim 7 further comprising a touch sensor.

9. The flexible display device according to claim 7 or 8, further comprising a polarizer.

Citation Information

Patent Citations

  • Tetracarboxylic acid or polyesterimide thereof, and method for production of the same

    JP2007284414A

  • Thin film transistor substrate and method of manufacturing thin film transistor

    JP2011222780A

  • TRANSPARENT POLYAMIDE-IMIDE RESIN AND FILM USING THE SAME

    JP2017503887A

  • Polyamic acid solution and transparent polyimide resin film based on the same

    JP2019112632A

  • Polyamide-imide copolymer and polyamide-imide film containing the same

    JP2019510847A